Metal-supported catalysts, battery electrodes and batteries
By using carbon support and catalyst metal particles supported on the carbon support, partially buried on the inner surface of the pores of the carbon support, a catalyst with excellent catalytic activity and durability was prepared, and the problem of insufficient catalyst activity and durability in the prior art was solved.
Patent Information
- Application Number
- CN202180062281.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-10
- Filing Date
- 2021-08-10
- Publication Date
- 2025-05-06
- Estimated Expiration
- 2041-08-10
AI Technical Summary
It is difficult to obtain metal-supported catalysts with excellent catalytic activity and durability in the prior art.
By preparing the catalyst using a carbon support and catalyst metal particles supported on the carbon support, the carbon structure in the catalyst exhibits half-maximum and half-width of the D band in the Raman spectrum of 53.0 cm-1 or less, and partially buried in the inner surface of the pores of the carbon support.
Excellent catalytic activity and durability of the catalyst are achieved, the ratio of the number average particle size to the average pore size of the catalyst metal particles is between 0.70 and 1.30, and the maximum desorption/adsorption ratio of the nitrogen adsorption isotherms is 1.05 or less.
Smart Images

Figure CN116113495B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to metal supported catalysts, battery electrodes and batteries. Background Art
[0002] In Patent Document 1, a catalyst for a fuel cell is described, including a catalyst supported on a carrier, wherein the catalyst for a fuel cell has a value of average pore diameter of the catalyst carrier / catalyst metal particle diameter (PGM) of 0.5 or more and 1.8 or less.
[0003] Patent Document 2 describes a catalyst composed of a catalyst carrier and a catalyst metal supported on the catalyst carrier, wherein the specific surface area of the catalyst per unit weight of the carrier is 715 m 2 / g-support or more, and the amount of acidic groups per unit support weight in the catalyst is 0.75 mmol / g-support or less.
[0004] In Patent Document 3, a polymer electrolyte fuel cell electrode catalyst having the following configurations (1) and (2) is described: (1) The polymer electrolyte fuel cell electrode catalyst includes a support formed of a conductive material and catalyst particles supported on the surface of the support. (2) The carrier has interconnected mesopores and satisfies the relationship of the following expression: 1.0≤ΔVdes / ΔVads≤1.14 (wherein ΔVdes=Vdes(0.49)–Vdes(0.01), ΔVads=Vads(0.49)–Vads(0.01), Vdes(0.49) represents the adsorption amount of the nitrogen adsorption isotherm in the mesopore region at a relative pressure of P / P0=0.49 during the desorption process, Vdes(0.01) represents the adsorption amount of the nitrogen adsorption isotherm in the micropore region at a relative pressure of P / P0=0.01 during the desorption process, Vads(0.49) represents the adsorption amount of the nitrogen adsorption isotherm in the mesopore region at a relative pressure of P / P0=0.49 during the adsorption process, and Vads(0.01) represents the adsorption amount of the nitrogen adsorption isotherm in the micropore region at a relative pressure of P / P0=0.01 during the adsorption process).
[0005] In patent document 4, a catalyst for a polymer electrolyte fuel cell is described, comprising catalyst particles (each of which is formed of platinum, cobalt, and manganese) supported on a carbon powder carrier, wherein the catalyst particles each have a composition ratio of platinum, cobalt, and manganese of Pt:Co:Mn=1:0.25 to 0.28:0.07 to 0.10 in a molar ratio, and the catalyst particles have an average particle size of 3.4 to 5.0 nm, and further, in the particle size distribution of the catalyst particles, the proportion of catalyst particles each having a particle size of 3.0 nm or less in all catalyst particles is 37% or less based on the number of particles, wherein at least the surface of each of the catalyst particles is loaded with a fluorine compound having a CF bond.
[0006] Citation List
[0007] Patent Literature
[0008] [PTL 1] WO 2007 / 055411 A1
[0009] [PTL 2] WO2014 / 175105A1
[0010] [PTL 3] JP 2017-091812 A
[0011] [PTL 4] WO 2019 / 065443 A1 Summary of the invention
[0012] Technical issues
[0013] However, it has been difficult to obtain metal-supported catalysts having excellent catalytic activity and durability.
[0014] The present invention has been made in view of the above-mentioned problems, and one of the objects of the present invention is to provide a metal-supported catalyst, a battery electrode, and a battery each having excellent catalytic activity and durability.
[0015] Solution to the problem
[0016] In order to achieve the above object, according to one embodiment of the present invention, there is provided a metal-supported catalyst, comprising: a carbon support; and catalyst metal particles supported on the carbon support, wherein the metal-supported catalyst comprises a carbon structure, the carbon structure exhibiting a Raman spectrum of 53.0 cm -1 or less half-width at half maximum of the D band at 1,340 cm -1There is a peak near the carbon support, and the metal-supported catalyst includes catalyst metal particles partially buried in the inner surface of the pores of the carbon support. According to one embodiment of the present invention, a metal-supported catalyst having both excellent catalytic activity and durability is provided.
[0017] In the metal-supported catalyst, the ratio of the number average particle size of the catalyst metal particles to the average pore size of the metal-supported catalyst may be 0.70 or more and 1.30 or less. When the relative pressure of the nitrogen adsorption isotherm of the metal-supported catalyst is in the range of 0.4 or more and 0.6 or less, the maximum value of the ratio of the nitrogen adsorption amount of the desorption side isotherm to the nitrogen adsorption amount of the adsorption side isotherm may be 1.05 or less. In the metal-supported catalyst, the ratio of the number of catalyst metal particles supported on the outer surface of the carbon support to the total number of catalyst metal particles supported on the carbon support may be 33% or less.
[0018] In the metal-supported catalyst, the number average particle diameter of the catalyst metal particles may be 1.50 nm or more and 4.00 nm or less. In the metal-supported catalyst, the volume average particle diameter of the catalyst metal particles may be 2.00 nm or more and 6.50 nm or less.
[0019] The metal-supported catalyst may have 200 (m 2 The metal-supported catalyst may have a BET specific surface area (m2 / g-carbon support) of 0.080 or less obtained by a water vapor adsorption method. 2 / g-carbon support) and the BET specific surface area obtained by nitrogen adsorption method (m 2 / g-carbon support) ratio.
[0020] In the metal-supported catalyst, the carbon support may have a median diameter of 1.00 μm or less. In the metal-supported catalyst, the metal-supported catalyst may have a median diameter of 0.50 (cm 3 In the metal-supported catalyst, the metal-supported catalyst may have a ratio of the volume of pores each having a pore size of less than 5 nm to the volume of pores each having a pore size of 5 nm or more of 1.80 or more.
[0021] In the metal-supported catalyst, the ratio of the number of catalyst metal particles supported at a position having a depth of 20 nm or more from the outer surface of the carbon support to the total number of catalyst metal particles supported on the carbon support may be 11% or more. In the metal-supported catalyst, the catalyst metal particles may be platinum particles.
[0022] To achieve the above object, according to one embodiment of the present invention, a battery electrode including a metal-supported catalyst is provided. According to one embodiment of the present invention, a battery electrode having excellent catalytic activity and durability is provided.
[0023] To achieve the above object, according to one embodiment of the present invention, a battery including a battery electrode is provided. According to one embodiment of the present invention, a battery having excellent catalytic activity and durability is provided.
[0024] Advantageous Effects of the Invention
[0025] According to the present invention, there are provided a metal-supported catalyst, a battery electrode, and a battery, each of which has excellent catalytic activity and durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is an explanatory diagram schematically showing the relationship between the size of the pores of the carbon support in the metal-supported catalyst and the size and arrangement of the catalyst metal particles supported on the carbon support.
[0027] Figure 2 is an explanatory diagram showing an example of a nitrogen adsorption isotherm obtained by a nitrogen adsorption method of a metal-supported catalyst.
[0028] Figure 3 is an explanatory diagram showing an example of a Raman spectrum obtained by Raman spectroscopy of a metal-supported catalyst.
[0029] Figure 4 It is an explanatory diagram showing an example of the results obtained by peak separation of a (111) diffraction line of platinum having a peak top at a position near a diffraction angle (2θ) of 40° in an X-ray diffraction pattern of a metal-supported catalyst.
[0030] Figure 5 is an explanatory diagram showing an example of a three-dimensionally reconstructed particle image obtained by electron beam tomography of a metal-supported catalyst.
[0031] Fig. 6A is an explanatory diagram showing an example of a three-dimensionally reconstructed image of a carbon support of a metal-supported catalyst obtained by electron beam tomography.
[0032] Figure 6B It shows that from Fig. 6A The three-dimensional reconstructed image shown is an explanatory diagram of an example of a three-dimensional reconstructed image of a cube obtained.
[0033] Figure 6C Included is a diagram showing Figure 6B An explanatory diagram showing an example of three cross-sectional images obtained from a three-dimensional reconstructed image of a cube.
[0034] Fig.6D It shows that Figure 6C Illustration of the void path identified in one of the cross-sectional images shown.
[0035] Fig. 6E It is an explanatory diagram for schematically illustrating an example of determining a gap path.
[0036] Fig. 6F This is an explanatory diagram schematically showing the length of a void path and the shortest straight-line distance in a three-dimensional reconstructed image of a cube.
[0037] Figure 7 : are explanatory diagrams showing the characteristics of the metal-supported catalyst, the performance of the battery, and the evaluation results of the catalytic activity of the carbon support. DETAILED DESCRIPTION
[0038] One of the embodiments of the present invention will be described below. The present invention is not limited to the examples described in the embodiment.
[0039] The metal-supported catalyst according to an embodiment of the present invention (hereinafter referred to as "the catalyst of the present invention") is a metal-supported catalyst comprising: a carbon support; and catalyst metal particles supported on the carbon support, wherein the metal-supported catalyst comprises a carbon structure that exhibits a Raman spectrum at 53.0 cm-1. -1 or less half-width at half maximum of the D band at 1,340 cm -1 There is a peak near the carbon support, and the metal-supported catalyst therein includes catalyst metal particles partially buried in the inner surface of the pores of the carbon support.
[0040] The catalyst of the present invention includes a carbon carrier and catalyst metal particles supported on the carbon carrier. It is preferred that the catalyst of the present invention is mainly formed by a carbon carrier and catalyst metal particles. The ratio of the sum of the weight of the carbon carrier contained in the catalyst of the present invention and the weight of the catalyst metal particles contained in the catalyst of the present invention to the weight of the catalyst of the present invention can be, for example, 90% by weight or more (90% by weight or more and 100% by weight or less), preferably 95% by weight or more, and particularly preferably 98% by weight or more. The ratio of the sum of the weight of the carbon carrier contained in the catalyst of the present invention and the weight of the catalyst metal particles contained therein to the weight of the catalyst of the present invention is obtained by thermogravimetric analysis (TG).
[0041] The carbon support contained in the catalyst of the present invention is a carbon material mainly formed of carbon. The carbon content of the carbon support can be, for example, 70% by weight or more (70% by weight or more and 100% by weight or less), and is preferably 75% by weight or more, more preferably 80% by weight or more, and particularly preferably 85% by weight or more. The carbon content of the carbon support is obtained by elemental analysis (combustion method) of the carbon support.
[0042] The carbon support is preferably a porous carbon material. In this case, the carbon support preferably contains pores with high interconnectivity. That is, the carbon support is preferably a carbon material having many interconnected pores.
[0043] The carbon support may be a carbonized material. The carbonized material is obtained by carbonizing a raw material containing an organic substance. The content of the organic substance in the raw material for carbonization may be, for example, 5 wt % or more and 90 wt % or less, and preferably 10 wt % or more and 80 wt % or less.
[0044] The organic substance contained in the raw material is not particularly limited as long as the organic substance can be carbonized. The organic compound contained in the organic substance may be a polymer (eg, a thermosetting resin and / or a thermoplastic resin), and / or may be an organic compound having a relatively small molecular weight.
[0045] Specifically, the organic substance can be, for example, one or more selected from the group consisting of: polyacrylonitrile; polyacrylonitrile-polyacrylic acid copolymer; polyacrylonitrile-polymethyl acrylate copolymer; polyacrylonitrile-polymethacrylic acid copolymer; polyacrylonitrile-polymethacrylic acid-polymethylallyl sulfonic acid copolymer; polyacrylonitrile-polymethyl methacrylate copolymer; phenol resin; polyfurfuryl alcohol; furan; furan resin; phenolic resin; melamine; melamine resin; epoxy resin; nitrogen-containing chelating resin (for example, selected from the group consisting of polyamine chelating resin; iminodiacetic acid chelating resin; aminophosphoric acid chelating resin and aminomethylphosphonic acid chelating resin); polyamide-imide resin; pyrrole; polypyrrole; polyvinylpyrrole; 3-methylpolypyrrole; acrylonitrile; polyvinylidene chloride olefins; thiophenes; oxazoles; thiazoles; pyrazoles; vinylpyridines; polyvinylpyridines; pyridazines; pyrimidines; piperazines; pyrans; morpholine; imidazoles; 1-methylimidazoles; 2-methylimidazoles; quinoxalines; anilines; polyanilines; succinic acid dihydrazides; adipic acid dihydrazides; polysulfones; polyaminobismaleimides; polyimides; polyvinyl alcohols; polyvinyl butyrals; benzimidazoles; polybenzimidazoles; polyamides; polyesters; polylactic acid; polyethers; polyetheretherketones; cellulose; carboxymethylcellulose; lignin; chitin; chitosan; pitch; silk; wool; polyamino acids; nucleic acids; DNA; RNA; hydrazines; hydrazides; ureas; salens; polycarbazoles; polybismaleimides; triazines; polyacrylic acids; polyacrylates; polymethacrylates; polymethacrylic acids; polyurethanes; polyamidoamines and polycarbodiimides.
[0046] The carbon carrier preferably contains nitrogen. That is, in this case, the carbon carrier contains nitrogen atoms in its carbon structure. The nitrogen-containing carbon carrier is preferably a nitrogen-containing carbonized material. The nitrogen-containing carbonized material is obtained by carbonizing a raw material containing a nitrogen-containing organic substance. The nitrogen-containing organic substance preferably contains a nitrogen-containing organic compound. The nitrogen-containing organic compound is not particularly limited as long as the organic compound contains nitrogen atoms in its molecule. In addition, the nitrogen contained in the carbon carrier may be nitrogen introduced by a nitrogen doping treatment.
[0047] The nitrogen content of the carbon carrier may be, for example, 0.10 wt% or more, and is preferably 0.15 wt% or more, more preferably 0.20 wt% or more, still more preferably 0.25 wt% or less, and particularly preferably 0.30 wt% or more. The upper limit of the nitrogen content of the carbon carrier is not particularly limited, but the nitrogen content may be, for example, 10.00 wt% or less. The nitrogen content of the carbon carrier is obtained by elemental analysis (combustion method) of the carbon carrier.
[0048] Carbonization in the production of carbonized materials is performed by heating the raw material and maintaining the raw material at a temperature at which the organic matter contained therein is carbonized (hereinafter referred to as "carbonization temperature"). The carbonization temperature is not particularly limited as long as the raw material is carbonized at the temperature, and may be, for example, 300°C or higher, and preferably 700°C or higher, more preferably 900°C or higher, still more preferably 1000°C or higher, and particularly preferably 1100°C or higher. The upper limit value of the carbonization temperature is not particularly limited, but the carbonization temperature may be, for example, 3,000°C or lower.
[0049] The temperature rise rate to the carbonization temperature is not particularly limited, and may be, for example, 0.5°C / min or more and 300°C / min or less. In the carbonization, the time period for which the raw material is kept at the carbonization temperature may be, for example, 1 second or more and 24 hours or less, preferably 5 minutes or more and 24 hours or less. The carbonization is preferably carried out in an inert atmosphere such as a nitrogen atmosphere.
[0050] Carbonization can be carried out under normal pressure (atmospheric pressure), but is preferably carried out under pressure (at a pressure higher than atmospheric pressure). When carbonization is carried out under pressure, the pressure of the atmosphere used for carbonization can be, for example, 0.05MPa or more in terms of gauge pressure, and preferably 0.15MPa or more, more preferably 0.20MPa or more, still more preferably 0.40MPa or more, particularly preferably 0.50MPa or more in terms of gauge pressure. The upper limit value of the pressure of the atmosphere used for carbonization is not particularly limited, but the pressure can be, for example, 10.00MPa or less.
[0051] The carbon support may be a carbonized material obtained by carbonizing a raw material containing an organic substance and a metal. In this case, the carbon support may be a carbonized material subjected to a metal removal treatment after carbonization. The metal removal treatment is a treatment for reducing the amount of metal derived from the raw material contained in the carbonized material. Specifically, the metal removal treatment is preferably, for example, a washing treatment with an acid and / or an electrolytic treatment.
[0052] When the carbon carrier is a carbonized material obtained by carbonizing a raw material containing an organic substance and a metal, the carbon carrier contains a metal derived from the raw material for carbonization (hereinafter referred to as "raw metal"). In this case, the carbon carrier contains the raw metal inside its skeleton. That is, the carbon carrier contains the raw metal inside the skeleton forming its porous structure. Even when the carbon carrier is a carbonized material produced by a metal removal process as described above, the raw metal remains in the skeleton of the carbon carrier. Among the raw metals contained in the carbon carrier, the weight of the raw metal contained inside the skeleton of the carbon carrier may be greater than the weight of the raw metal contained in the surface of the skeleton of the carbon carrier.
[0053] The raw metal within the framework of the carbon support can be detected by subjecting the framework to a surface etching treatment and analyzing the cross section exposed by the etching treatment. That is, when one particle of the carbon support is subjected to an etching treatment, the raw metal is detected in the cross section of the particle exposed by the etching treatment. The raw metal contained in the carbon support can be detected by, for example, inductively coupled plasma mass spectrometry (ICP-MS) of the carbon support.
[0054] The raw metal content of the carbon carrier (the ratio of the weight of the raw metal contained in the carbon carrier to the weight of the carbon carrier) can be, for example, 0.01 wt % or more, 0.03 wt % or more, or 0.05 wt % or more. In addition, the raw metal content of the carbon carrier can be, for example, 5.00 wt % or less, 4.00 wt % or less, or 3.00 wt % or less. The raw metal content of the carbon carrier can be specified by any combination of any of the above lower limits and any of the above upper limits. The raw metal content of the carbon carrier is obtained by ICP-MS of the carbon carrier.
[0055] The carbon support is preferably a carbon material showing catalytic activity. That is, the carbon support is preferably a carbon catalyst that shows catalytic activity alone. The carbon catalyst is preferably a carbonized material containing a raw material metal, which is obtained by carbonizing a raw material containing an organic substance and a metal as described above.
[0056] The catalytic activity exhibited by the carbon catalyst is, for example, preferably reduction activity and / or oxidation activity, more preferably oxygen reduction activity and / or hydrogen oxidation activity, and particularly preferably at least oxygen reduction activity.
[0057] Specifically, when a voltage of 0.7 V (vs. NHE) is applied in the oxygen reduction voltammogram, the carbon support can exhibit a 0.01 (mA / cm 2 ) or greater reduction current density I 0.7 The oxygen reduction activity of the oxygen reduction voltammogram was obtained by using a rotating disk electrode apparatus, which includes a 0.1 mg / cm 2 The carbon support preferably exhibits a density of 0.05 (mA / cm 2 ) or greater reduction current density I 0.7 The oxygen reduction activity of 0.08 (mA / cm 2 ) or greater reduction current density I 0.7 The oxygen reduction activity of 0.7 The upper limit of is not particularly limited, but may be, for example, 7.00 (mA / cm 2 ) or smaller.
[0058] In addition, when there is –10μA / cm in the oxygen reduction voltammogram 2 When a reduction current of 200 Hz flows, the carbon support may exhibit an oxygen reduction starting potential E of 0.35 (V, relative to NHE) or more. O2 The oxygen reduction activity of the oxygen reduction voltammogram was obtained by using a rotating disk electrode apparatus, which includes a 0.1 mg / cm 2 The carbon support preferably exhibits an oxygen reduction onset potential E of 0.50 (V, relative to NHE) or more. O2 and particularly preferably exhibit an oxygen reduction onset potential E of 0.65 (V, relative to NHE) or more. O2 Oxygen reduction activity. Oxygen reduction starting potential E O2 The upper limit value of is not particularly limited, but may be, for example, 1.23 (V vs. NHE) or less.
[0059] It is assumed that the catalytic activity exhibited by the carbon catalyst obtained by carbonizing a raw material containing organic matter and metal is mainly caused by the active sites contained in the unique carbon structure formed by carbonization rather than the raw metal contained in the carbon catalyst. The above is supported by the following facts: even when the carbonized material obtained by carbonization is subjected to a metal removal treatment to reduce the content of its raw metal, the catalytic activity of the carbonized material after the metal removal treatment is not significantly reduced compared with the catalytic activity before the metal removal treatment; and unlike the carbonized material obtained by carbonizing a raw material containing organic matter and metal, the carbon material obtained by loading a metal on the surface of the carbonized material (which is obtained by carbonizing a raw material containing organic matter but not metal) does not have excellent catalytic activity.
[0060] The raw material metal is preferably a transition metal. That is, the raw material metal may be a transition metal belonging to Groups III to XII of the periodic table. The raw material metal may be a transition metal other than platinum. In addition, the raw material metal may be a transition metal other than a noble metal (e.g., ruthenium (Ru), palladium (Pd), rhodium (Rh), silver (Ag), osmium (Os), iridium (Ir), platinum (Pt) and gold (Au)). The raw material metal is preferably a transition metal belonging to the fourth period of Groups III to XII of the periodic table.
[0061] Specifically, the raw material metal can be one or more selected from the group consisting of scandium (Sc); titanium (Ti); vanadium (V); chromium (Cr); manganese (Mn); iron (Fe); cobalt (Co); nickel (Ni); copper (Cu); zinc (Zn); yttrium (Y); zirconium (Zr); niobium (Nb); molybdenum (Mo); ruthenium (Ru); rhodium (Rh); palladium (Pd); silver (Ag); lanthanides (e.g., gadolinium (Gd)); and actinides, and is preferably one or more selected from the group consisting of Fe; Co; Ni; Cu and Zn, and particularly preferably one or more selected from the group consisting of Fe; Co; Ni and Zn.
[0062] The particle size of the carbon carrier is not particularly limited, but, for example, the median diameter of the carbon carrier may be 1.00 μm or less, and is preferably 0.80 μm or less, more preferably 0.55 μm or less, still more preferably 0.50 μm or less, and particularly preferably 0.45 μm or less. The lower limit of the median diameter of the carbon carrier is not particularly limited, but the median diameter may be, for example, 0.05 μm or more. The particle size of the carbon carrier is obtained by a laser diffraction method of the carbon carrier.
[0063] The catalyst metal particles contained in the catalyst of the present invention are not particularly limited as long as the metal particles exhibit catalytic activity, but for example, metal particles exhibiting reduction activity and / or oxidation activity are preferred, metal particles exhibiting oxygen reduction activity and / or hydrogen oxidation activity are more preferred, and metal particles exhibiting at least oxygen reduction activity are particularly preferred.
[0064] Specifically, the catalyst metal particles are preferably metal particles containing a noble metal (hereinafter referred to as "noble metal particles"). The noble metal particles contain pure noble metal (noble metal not alloyed) and / or noble metal alloys. The catalyst metal particles (e.g., noble metal particles) may not contain the same type of metal as the raw material metal.
[0065] The noble metal is preferably one or more selected from the group consisting of Ru, Pd, Rh, Ag, Os, Ir, Pt and Au, more preferably one or more selected from the group consisting of Ru, Pd, Rh and Ir, and particularly preferably Pt. That is, the noble metal particles are particularly preferably Pt particles. The Pt particles contain pure Pt and / or a Pt alloy.
[0066] The noble metal alloy is an alloy of one or more noble metals and one or more non-noble metals. The non-noble metal is not particularly limited as long as the metal is a metal other than a noble metal and forms an alloy with the noble metal, but is preferably a transition metal. Specifically, the non-noble metal contained in the noble metal alloy is preferably selected from one or more of the group consisting of Cu, Mn, Ce, Au, Pd, Ru, Nb, Ti, Fe, Co, and Ni, more preferably selected from one or more of the group consisting of Fe, Co, and Ni, and particularly preferably selected from one or more of the group consisting of Co and Ni.
[0067] The content of the precious metal in the precious metal particles (the ratio of the weight of the precious metal contained in the precious metal particles (when containing two or more precious metals, the total weight of the two or more precious metals) to the weight of the precious metal particles) is not particularly limited as long as the content falls within the range for obtaining the effect of the present invention, but may be, for example, 50 wt% or more (50 wt% or more and 100 wt% or less), and is preferably 75 wt% or more, more preferably 85 wt% or more, and particularly preferably 90 wt% or more. The precious metal content of the precious metal particles is obtained by ICP-MS.
[0068] When the catalyst metal particles are noble metal particles, the content of the noble metal in the catalyst of the present invention (the ratio of the weight of the noble metal contained in the catalyst of the present invention to the weight of the catalyst of the present invention) can be, for example, 1.0 wt % or more, and preferably 3.0 wt % or more, more preferably 5.0 wt % or more, still more preferably 10.0 wt % or more, and particularly preferably 15.0 wt % or more. The noble metal content of the catalyst of the present invention can be, for example, 60.0 wt % or less. The noble metal content of the metal-supported catalyst is obtained by ICP-MS.
[0069] When the catalyst metal particles are noble metal particles and the catalyst of the present invention contains non-noble metals (for example, when the noble metal particles contain noble metal alloys, non-noble metals contained in the noble metal alloys; and / or raw metals when the carbon support contains raw metals as non-noble metals), the molar ratio of the noble metal to the non-noble metal contained in the catalyst of the present invention (hereinafter referred to as "noble metal / non-noble metal molar ratio") can be, for example, 0.3 or greater, and preferably 0.5 or greater, more preferably 1.0 or greater, still more preferably 3.0 or greater, and particularly preferably 4.0 or greater. The noble metal / non-noble metal molar ratio of the catalyst of the present invention can be, for example, 20.0 or less, and preferably 15.0 or less, particularly preferably 10.0 or less. The noble metal / non-noble metal molar ratio can be specified by arbitrarily combining any one of the above lower limits and any one of the above upper limits. The noble metal / non-noble metal molar ratio of the metal-supported catalyst is obtained by ICP-MS.
[0070] In the catalyst of the present invention, the number average particle size of the catalyst metal particles may be, for example, 1.50 nm or more and 4.00 nm or less, and preferably 1.90 nm or more and 3.70 nm or less, more preferably 2.10 nm or more and 3.50 nm or less, still more preferably 2.10 nm or more and 3.25 nm or less, particularly preferably 2.10 nm or more and 3.10 nm or less. The number average particle size of the catalyst metal particles is obtained by X-ray diffraction.
[0071] In the catalyst of the present invention, the volume average particle size of the catalyst metal particles may be, for example, 2.00 nm or more and 6.50 nm or less, and preferably 2.30 nm or more and 5.70 nm or less, more preferably 2.30 nm or more and 5.40 nm or less, still more preferably 2.30 nm or more and 5.15 nm or less, particularly preferably 2.40 nm or more and 5.00 nm or less. The volume average particle size of the catalyst metal particles is obtained by X-ray diffraction.
[0072] The catalyst of the present invention has a carbon structure that exhibits a 53.0 cm -1 or less of the half-width at half maximum of the D band in the Raman spectrum obtained by Raman spectroscopy (hereinafter referred to as "Raman D half-width at half maximum"), the D band at 1,340 cm -1 Nearby (e.g., at 1,330 cm -1 or larger and 1,350cm -1 or smaller) has a peak.
[0073] The Raman D half-peak half-width of the catalyst of the present invention is preferably 52.0 cm -1 or less, more preferably 51.0 cm -1 or less, particularly preferably 50.0 cm -1 The lower limit of the half width at half maximum of the Raman D of the catalyst of the present invention is not particularly limited, but the half width at half maximum may be, for example, 20.0 cm -1 or larger, and preferably 25.0 cm -1 or larger, particularly preferably 30.0 cm -1 The Raman D half-peak half width of the catalyst of the present invention can be specified by arbitrarily combining any one of the above lower limits with any one of the above upper limits.
[0074] In the Raman spectrum, the D band is a component derived from a curved structure including defects and edges. The half-width at half maximum of the D band represents the crystallinity of the curved structure contained in the carbon structure. That is, the small half-width at half-maximum of the D band means that the crystallinity of the curved structure is high. Therefore, the Raman D half-width at half-maximum of the carbon structure of the catalyst of the present invention (specifically, the carbon structure of the carbon carrier) falling within the above range means that the carbon structure contains a curved structure with a relatively high crystallinity. The catalyst of the present invention includes a carbon structure containing a curved structure with a relatively high crystallinity that contributes to the excellent durability and oxidation resistance of the catalyst of the present invention.
[0075] In addition, the catalyst of the present invention includes catalyst metal particles partially buried in the inner surface of the pores of the carbon carrier. That is, in the catalyst of the present invention, at least some of the catalyst metal particles supported on the carbon carrier are supported in the pores of the carbon carrier, and each of them is partially buried in the inner surface of the pores.
[0076] exist Figure 1 In FIG. 1 , the relationship between the size of the pores of the carbon support and the size and arrangement of the catalyst metal particles supported on the carbon support is schematically shown. Figure 1 In the embodiment, the catalyst metal particles D are supported in the pores of the carbon support, and a part of them is buried in the inner surface of the pores. It should be noted that Figure 1 These are merely schematic illustrations, and, for example, the relative relationship between the size of the carbon support and the size of the pores and the catalyst metal particles, and the shape of the pores of the carbon support are not necessarily the same as the actual ones.
[0077] The catalyst of the present invention contains catalyst metal particles (such as catalyst metal particles D) partially buried in the inner surface of the pores, for example, which is supported by the following: the ratio of the number average particle size of the catalyst metal particles to the average pore size of the catalyst of the present invention (hereinafter referred to as the "catalyst metal particle size / pore size ratio") is 0.70 or greater and 1.30 or less; when the relative pressure of the nitrogen adsorption isotherm of the catalyst of the present invention is in the range of 0.4 or greater and 0.6 or less, the maximum value of the ratio of the nitrogen adsorption amount of the desorption side isotherm to the nitrogen adsorption amount of the adsorption side isotherm (hereinafter referred to as the "N2 desorption / adsorption amount ratio") is 1.05 or less; and in the catalyst of the present invention, the ratio of the number of catalyst metal particles loaded on the outer surface of the carbon carrier to the total number of catalyst metal particles loaded on the carbon carrier (hereinafter referred to as the "catalyst metal loading ratio at the outer surface") is 33% or greater (the catalyst metal particle size / pore size ratio, the N2 desorption / adsorption amount ratio, and the catalyst metal loading ratio at the outer surface of the catalyst of the present invention are described later).
[0078] That is, in the catalyst of the present invention, although more catalyst metal particles having a particle size close to the diameter of the pores of the carbon carrier are loaded inside the carbon carrier than on the outer surface of the carbon carrier, when the pores in which the catalyst metal particles are loaded are interconnected, it is strongly recommended that the catalyst of the present invention include each of the catalyst metal particles buried in the inner surface of the pores.
[0079] Specifically, Figure 1 As shown, when the catalyst metal particles A having a particle size close to the diameter of the pores of the carbon support are supported in the carbon support and are not buried in the inner surfaces of the pores, the catalyst metal particles A block the pores and thus the interconnectivity of the pores is lost.
[0080] The catalyst metal particles B having a particle size sufficiently smaller than the diameter of the pores of the carbon support do not block the pores even when loaded inside the carbon support, and therefore, the interconnectivity of the pores is maintained even if the catalyst metal particles B are not buried in the inner surface of the pores. The catalyst metal particles B′ having a particle size sufficiently larger than the diameter of the pores of the carbon support are loaded on the outer surface of the carbon support, and thus the interconnectivity of the pores is maintained. In addition, when the catalyst metal particles C having a particle size close to the diameter of the pores of the carbon support are loaded on the outer surface of the carbon support, the interconnectivity of the pores is maintained.
[0081] Different from the above, when the interconnectivity of the pores is maintained even if the catalyst metal particles D having a particle diameter close to the diameter of the pores of the carbon carrier are supported inside the carbon carrier, it can be assumed that the catalyst metal particles D are partially buried in the inner surface of the pores.
[0082] In the catalyst of the present invention, partial burying of the catalyst metal particles in the inner surface of the pores of the carbon support contributes to improving the stability of the catalyst metal particles in the pores.
[0083] The catalyst of the present invention has high catalytic activity and durability because it includes: a carbon support including a carbon structure showing a Raman D half-peak half width within the above range; and catalyst metal particles partially buried in the inner surface of pores of the carbon support.
[0084] Specifically, in the catalyst of the present invention, some catalyst metal particles are loaded on a carbon carrier in a state of being buried in the inner surface of pores containing a curved structure having a relatively high crystallinity, and therefore, for example, in a fuel cell including a cathode containing the catalyst of the present invention, while effectively preventing the electrolyte from poisoning the catalyst metal particles, the catalyst metal particles can be stably maintained, and thus high catalytic activity can be effectively maintained.
[0085] The average pore size of the catalyst of the present invention can be, for example, 2.00 nm or more and 5.00 nm or less, and is preferably 2.40 nm or more and 4.60 nm or less, more preferably 2.60 nm or more and 4.40 nm or less, still more preferably 2.80 nm or more and 4.20 nm or less, and particularly preferably 3.00 nm or more and 4.00 nm or less.
[0086] The average pore size of the metal-supported catalyst is obtained by the nitrogen adsorption method of the metal-supported catalyst. Specifically, by using the analysis software contained in the commercially available specific surface area / pore distribution measurement device, the average pore size of the metal-supported catalyst is obtained by the following equation: Average pore size of the metal-supported catalyst (nm) = 4×{total pore volume of the metal-supported catalyst (cm 3 / g-metal-supported catalyst)×10 21} / Specific surface area of metal-supported catalyst (m 2 / g-metal-supported catalyst)×10 18 .
[0087] The catalyst metal particle size / pore size ratio of the catalyst of the present invention (the ratio of the number average particle size of the catalyst metal particles of the catalyst of the present invention to the average pore size) is 0.70 or more and 1.30 or less. The catalyst metal particle size / pore size ratio of the catalyst of the present invention is, for example, preferably 0.72 or more and 1.20 or less, more preferably 0.75 or more and 1.10 or less, still more preferably 0.78 or more and 1.00 or less, particularly preferably 0.80 or more and 1.00 or less.
[0088] The catalyst metal particle size / pore size ratio of the catalyst of the present invention falling within the above range indicates that the particle size of many catalyst metal particles supported on the carbon support is close to the diameter of the pores of the carbon support.
[0089] When the relative pressure of the nitrogen adsorption isotherm of the catalyst of the present invention is in the range of 0.4 or greater and 0.6 or less, the catalyst of the present invention can exhibit a maximum value of the N2 desorption / adsorption ratio (the ratio of the nitrogen adsorption amount of the desorption side isotherm to the nitrogen adsorption amount of the adsorption side isotherm) of 1.05 or less.
[0090] In this case, in the nitrogen adsorption isotherm obtained by the nitrogen adsorption method (more specifically, the BET method) of the catalyst of the present invention, the N2 desorption / adsorption amount ratio obtained by dividing the nitrogen adsorption amount of the desorption side isotherm by the nitrogen adsorption amount of the adsorption side isotherm falls within the range of 1.05 or less at all measurement points, and at each of the measurement points, the relative pressure (P / P0) (which is the ratio of the adsorption equilibrium pressure (P) to the saturated vapor pressure (P0)) falls within the range of 0.4 or more and 0.6 or less. Due to its measurement principle, the N2 desorption / adsorption amount ratio takes a value of 1.00 or more.
[0091] The maximum value of the N2 desorption / adsorption amount ratio of the catalyst of the present invention is preferably 1.04 or less, more preferably 1.03 or less, further preferably 1.02 or less, and particularly preferably 1.01 or less.
[0092] The maximum value of the N2 desorption / adsorption amount ratio of the catalyst of the present invention falling within the above range means that the nitrogen adsorption isotherm of the catalyst of the present invention has substantially no hysteresis phenomenon, and indicates that the pores of the catalyst of the present invention have high interconnectivity (the catalyst of the present invention has many interconnected pores). That is, in the catalyst of the present invention, some catalyst metal particles are supported in the pores of the carbon support, but the pores supporting the catalyst metal particles maintain interconnectivity.
[0093] The catalyst metal loading ratio at the outer surface of the catalyst of the present invention (the ratio of the number of catalyst metal particles loaded on the outer surface of the carbon carrier to the total number of catalyst metal particles loaded on the carbon carrier) can be, for example, 40% or less, and is preferably 33% or less, more preferably 32% or less, still more preferably 31% or less, and particularly preferably 30% or less. The lower limit of the catalyst metal loading ratio at the outer surface of the catalyst of the present invention is not particularly limited, but the ratio can be, for example, 5% or more. The catalyst metal loading ratio at the outer surface of the catalyst of the present invention is obtained by electron beam tomography.
[0094] The catalyst metal loading ratio at the outer surface of the catalyst of the present invention falls within the above range, indicating that many catalyst metal particles contained in the catalyst of the present invention are loaded inside the carbon carrier. Compared with the catalyst metal particles loaded on the outer surface of the carbon carrier, the catalyst metal particles loaded inside the carbon carrier are not easy to deteriorate. Therefore, the small catalyst metal loading ratio at the outer surface of the catalyst of the present invention contributes to the catalytic activity and durability of the catalyst of the present invention.
[0095] In the catalyst of the present invention, the ratio of the number of catalyst metal particles loaded at a depth of 20 nm or more from the outer surface of the carbon carrier to the total number of catalyst metal particles loaded on the carbon carrier (hereinafter referred to as "the catalyst metal loading ratio at a depth of 20 nm or more") can be, for example, 11% or more, and is preferably 12% or more, more preferably 13% or more, still more preferably 14% or more, and particularly preferably 15% or more. The upper limit value of the "catalyst metal loading ratio at a depth of 20 nm or more" of the catalyst of the present invention is not particularly limited, but the ratio can be, for example, 50% or less. The "catalyst metal loading ratio at a depth of 20 nm or more" of the catalyst of the present invention is obtained by electron beam tomography.
[0096] The catalyst metal loading ratio at a depth of 20 nm or more of the catalyst of the present invention is calculated by the following equation: "Catalyst metal loading ratio at a depth of 20 nm or more (%) of the catalyst of the present invention = "the number of catalyst metal particles loaded at a depth of 20 nm or more from the outer surface of the carbon carrier" ÷ "the total number of catalyst metal particles loaded on the carbon carrier" × 100.
[0097] The total number of catalyst metal particles supported on the carbon support in the catalyst of the present invention is the sum of the number of catalyst metal particles supported on the outer surface of the carbon support and the number of catalyst metal particles supported inside the carbon support.
[0098] The number of catalyst metal particles supported at a position 20 nm or more from the outer surface of the carbon support in the catalyst of the present invention is equal to the number obtained by subtracting the number of catalyst metal particles supported at a position less than 20 nm from the outer surface of the carbon support from the number of catalyst metal particles supported inside the support.
[0099] The catalyst metal particles supported in the pores at a depth of 20 nm or more from the outer surface of the carbon support are less susceptible to deterioration than the catalyst metal particles supported on the outer surface and the catalyst metal particles supported at a position closer to the outer surface. Therefore, the fact that the "catalyst metal loading ratio at a depth of 20 nm or more" of the catalyst of the present invention is large contributes to the catalytic activity and durability of the catalyst of the present invention.
[0100] In the catalyst of the present invention, the ratio of the sum of the number of catalyst metal particles loaded on the outer surface of the carbon carrier and the number of catalyst metal particles loaded at a depth of 5 nm or less from the outer surface of the carbon carrier to the total number of catalyst metal particles loaded on the carbon carrier (hereinafter referred to as "the catalyst metal loading ratio at a depth of +5 nm or less on the outer surface") can be, for example, 60% or less, and is preferably 58% or less, more preferably 54% or less, still more preferably 52% or less, and particularly preferably 50% or less. The lower limit value of the "catalyst metal loading ratio at a depth of +5 nm or less on the outer surface" of the catalyst of the present invention is not particularly limited, but the ratio can be, for example, 10% or more. The catalyst metal loading ratio at a depth of +5 nm or less on the outer surface of the catalyst of the present invention is obtained by electron beam tomography.
[0101] The total pore volume of the catalyst of the present invention may be, for example, 0.50 (cm 3 / g-carbon support) or more, and preferably 0.70 (cm 3 / g-carbon support) or more, more preferably 0.85 (cm 3 / g-carbon support) is larger, and more preferably 0.90 (cm 3 / g-carbon support) or more, and particularly preferably 1.00 (cm 3 The upper limit of the total pore volume of the catalyst of the present invention is not particularly limited, but the total pore volume may be, for example, 5.00 (cm 3 / g-carbon support) or less. The total pore volume of the metal-supported catalyst is obtained by a nitrogen adsorption method (more specifically, a BJH method) of the metal-supported catalyst. The " / g-carbon support" in the numerical unit means that the value is per 1 g of the carbon support in the metal-supported catalyst.
[0102] The volume of pores each having a pore diameter of less than 5 nm (hereinafter referred to as "pore volume less than 5 nm") of the catalyst of the present invention may be, for example, 0.50 (cm 3 / g-carbon support) or more, and preferably 0.60 (cm 3 / g-carbon support) or more, more preferably 0.65 (cm 3 / g-carbon support) is larger, and particularly preferably 0.70 (cm 3 / g-carbon support) or more. The upper limit of the pore volume less than 5 nm of the catalyst of the present invention is not particularly limited, but the pore volume less than 5 nm may be, for example, 5.00 (cm 3 The pore volume of the metal-supported catalyst less than 5 nm is obtained by a nitrogen adsorption method (more specifically, a BJH method) of the metal-supported catalyst.
[0103] The fact that the pore volume of the catalyst of the present invention is large, which is smaller than 5 nm, contributes to the catalytic activity of the catalyst of the present invention. That is, for example, pores each having a relatively small pore size serve as locations for preferentially generating catalyst metal particles that exhibit high catalytic activity and have a relatively small particle size, and as a result, the pores contribute to the excellent catalytic activity of the catalyst of the present invention.
[0104] The volume of pores each having a pore diameter of 5 nm or more (hereinafter referred to as "5 nm or more pore volume") of the catalyst of the present invention may be, for example, 0.70 (cm 3 / g-carbon support) or less, and preferably 0.60 (cm 3 / g-carbon support) or less, more preferably 0.50 (cm 3 / g-carbon support) is smaller, and particularly preferably 0.45 (cm 3 / g-carbon support) or less. The lower limit of the pore volume of 5 nm or more of the catalyst of the present invention is not particularly limited, but the pore volume of 5 nm or more may be, for example, 0.10 (cm 3 The pore volume of 5 nm or more of the metal-supported catalyst is obtained by a nitrogen adsorption method (more specifically, a BJH method) of the metal-supported catalyst.
[0105] The ratio of the pore volume of the catalyst of the present invention less than 5 nm to the pore volume of the catalyst of the present invention of 5 nm or more (hereinafter referred to as "pore volume ratio of less than 5 nm pores / 5 nm or more pores") may be, for example, 1.80 or more, and preferably 1.90 or more, particularly preferably 2.00 or more. The upper limit of the pore volume ratio of less than 5 nm pores / 5 nm or more pores of the catalyst of the present invention is not particularly limited, but the pore volume ratio may be, for example, 15.00 or less.
[0106] For example, when the catalyst of the present invention contains many pores each having a pore size of less than 5 nm, the degradation of the catalyst metal particles supported in the pores of the catalyst of the present invention (for example, oxidation of the catalytic metal supported in the pores due to water entering the pores) is effectively suppressed.
[0107] The BET specific surface area of the catalyst of the present invention obtained by the nitrogen adsorption method (hereinafter referred to as "N2-BET specific surface area") can be, for example, 200 (m 2 / g-carbon carrier) or more, and preferably 600 (m 2 / g-carbon carrier) or more, more preferably 900 (m 2 / g-carbon carrier) or more, still more preferably 1000 (m 2 / g-carbon support) or more, particularly preferably 1,100 (m 2The upper limit of the N2-BET specific surface area of the catalyst of the present invention is not particularly limited, but the N2-BET specific surface area may be, for example, 3,000 (m 2 / g-carbon support) or less.
[0108] The BET specific surface area (m 2 / g-carbon support) and the N2-BET specific surface area (m 2 The ratio of the water vapor-BET / nitrogen-BET specific surface area ratio (g-carbon support) (hereinafter referred to as "water vapor-BET / nitrogen-BET specific surface area ratio") can be, for example, 0.080 or less, and is preferably 0.070 or less, more preferably 0.060 or less, still more preferably 0.050 or less, and particularly preferably 0.045 or less. The lower limit value of the water vapor-BET / nitrogen-BET specific surface area ratio of the catalyst of the present invention is not particularly limited, but the specific surface area ratio can be, for example, 0.010 or more.
[0109] The fact that the water vapor-BET / nitrogen-BET specific surface area ratio of the catalyst of the present invention is small indicates that the hydrophobicity of the pores of the catalyst of the present invention is high. Therefore, the small water vapor-BET / nitrogen-BET specific surface area ratio of the catalyst of the present invention inhibits excessive penetration of water into the pores of the catalyst of the present invention, and / or facilitates the discharge of water generated in the pores to the outside of the pores by chemical reaction.
[0110] The catalyst of the present invention may have a tortuosity of 1.90 or less, preferably 1.85 or less, and particularly preferably 1.80 or less. The lower limit of the tortuosity of the catalyst of the present invention is not particularly limited, but the tortuosity may be, for example, 1.50 or greater. The tortuosity of the catalyst of the present invention is obtained by electron beam tomography.
[0111] When the tortuosity of the catalyst of the present invention falls within the above range, diffusion and transport of substances (for example, diffusion of gas and transport of protons in the pores of the catalyst of the present invention included in the cathode of a fuel cell) are effectively performed in the interconnected pores of the catalyst of the present invention.
[0112] The catalyst of the present invention preferably contains nitrogen. In this case, the catalyst of the present invention preferably includes a nitrogen-containing carbon carrier. The nitrogen content of the catalyst of the present invention can be, for example, 0.05% by weight or more, and is preferably 0.10% by weight or more, more preferably 0.15% by weight or more, still more preferably 0.20% by weight or more, and particularly preferably 0.25% by weight or more. The upper limit value of the nitrogen content of the catalyst of the present invention is not particularly limited, but the nitrogen content can be, for example, 4.00% by weight or less. The nitrogen content of the catalyst of the present invention is obtained by elemental analysis (combustion method).
[0113] The catalyst of the present invention exhibits catalytic activity derived from the catalyst metal particles supported on the carbon support. In addition, when the carbon support itself exhibits catalytic activity alone (when the carbon support is a carbon catalyst), the catalyst of the present invention exhibits catalytic activity derived from the carbon support itself and catalytic activity derived from the catalyst metal particles.
[0114] The catalytic activity exhibited by the catalyst of the present invention is not particularly limited, but for example, it is preferably reduction activity and / or oxidation activity, more preferably oxygen reduction activity and / or hydrogen oxidation activity, and particularly preferably at least oxygen reduction activity.
[0115] The method for producing the catalyst of the present invention (hereinafter referred to as "the method of the present invention") includes supporting catalyst metal particles on a carbon carrier. The method for supporting the catalyst metal particles on the carbon carrier is not particularly limited as long as the effect of the present invention is obtained, but a gas phase reduction method is preferred. That is, the method of the present invention includes subjecting a carbon carrier on which a metal compound serving as a precursor of the catalyst metal particles is supported to a gas phase reduction treatment to form catalyst metal particles supported on the carbon carrier.
[0116] The method of the present invention preferably includes: a first step of subjecting a carbon support on which a metal compound serving as a precursor of catalyst metal particles is loaded, to a gas-phase reduction treatment to form catalyst metal particles loaded on the carbon support; and a second step of heating the carbon support on which the catalyst metal particles are loaded in an inert atmosphere after the first step.
[0117] In this case, for example, by performing a second step including a heating treatment in an inert atmosphere after a first step including a gas phase reduction treatment, excessive aggregation of catalyst metal particles and / or excessive migration of catalyst metal particles from the interior of the carbon support to its outer surface can be effectively suppressed.
[0118] The method of supporting the metal compound serving as a precursor of the catalyst metal particles (hereinafter referred to as "precursor compound") on the carbon support is not particularly limited, but for example, a method comprising mixing the carbon support and the precursor compound in a liquid phase is preferably used. Specifically, for example, the carbon support is immersed in a solution containing the precursor compound to impregnate the pores of the carbon support with the precursor compound.
[0119] The precursor compound is not particularly limited as long as the precursor compound forms a catalyst metal for forming catalyst metal particles when reduced. That is, when noble metal particles are supported on a carbon support as catalyst metal particles, a noble metal compound that forms noble metal particles by reduction treatment is used as a precursor compound.
[0120] Specifically, when Pt particles are loaded on a carbon support as catalyst metal particles, for example, one or more selected from the group consisting of the following are preferably used as the Pt compound acting as a precursor compound: platinates (for example, one or more selected from the group consisting of chloroplatinic acid (H2PtCl6); and dinitrodiamineplatinum nitrate (Pt(NH3)2(NO2)2)); and bis(acetylacetonate)platinum.
[0121] The carbon support on which the precursor compound is supported which is subjected to the gas phase reduction treatment in the first step is preferably a dry solid. That is, for example, when the precursor compound is supported on the carbon support in a liquid phase, the carbon support on which the precursor compound is supported is obtained in a solid form by drying a solution containing the carbon support and the precursor compound.
[0122] In the gas phase reduction treatment, the carbon support on which the precursor compound is supported is heated in a reducing atmosphere. The reducing atmosphere in the gas phase reduction treatment is an atmosphere containing a reducing gas. The reducing gas is not particularly limited as long as the effect of the present invention is obtained, but for example, one or more selected from the group consisting of: hydrogen gas; ammonia gas; and hydrocarbon gas (e.g., one or more selected from methane gas, propane gas, and butane gas) is preferably used.
[0123] The content of reducing gas in the reducing atmosphere (when the atmosphere contains two or more reducing gases, the sum of the contents of two or more reducing gases) is not particularly limited as long as the content falls within the range for obtaining the effects of the present invention, but may be, for example, 1 volume % or more (1 volume % or more and 100 volume % or less), and is preferably 5 volume % or more, more preferably 10 volume % or more, and particularly preferably 20 volume % or more.
[0124] The temperature at which the carbon support on which the precursor compound is supported is heated in the gas phase reduction treatment (hereinafter referred to as the "first heating temperature") is not particularly limited as long as the first heating temperature falls within the range for obtaining the effect of the present invention, but may be, for example, 250°C or higher, and preferably 300°C or higher, more preferably 700°C or higher, still more preferably 775°C or higher, and particularly preferably 800°C or higher. The upper limit value of the first heating temperature is not particularly limited, but the first heating temperature may be, for example, 1200°C or lower, and preferably 1100°C or lower, and particularly preferably 1000°C or lower. The first heating temperature may be specified by arbitrarily combining any one of the above lower limits with any one of the above upper limits.
[0125] The time period (hereinafter referred to as "first heating time") for heating the carbon support on which the precursor compound is loaded at the above-mentioned first heating temperature in the gas phase reduction treatment is not particularly limited, as long as the first heating time falls within the range of obtaining the effect of the present invention, but may be, for example, 1 minute or longer, and preferably 5 minutes or longer, particularly preferably 10 minutes or longer. The upper limit value of the first heating time is not particularly limited, but the first heating time may be, for example, 180 minutes or shorter, and preferably 60 minutes or shorter, particularly preferably 40 minutes or shorter. The first heating time may be specified by arbitrarily combining any one of the above-mentioned lower limit values and any one of the above-mentioned upper limit values.
[0126] In the second step, the carbon support supporting the catalyst metal particles formed by the gas phase reduction treatment in the first step is subjected to a heat treatment in an inert atmosphere. The inert atmosphere is an atmosphere mainly formed of an inert gas. The inert gas is not particularly limited, but is preferably one or more selected from the group consisting of, for example, nitrogen; argon; and helium.
[0127] The content of the inert gas in the inert atmosphere (when the atmosphere contains two or more inert gases, the sum of the contents of the two or more inert gases) can be, for example, 95 volume % or more (95 volume % or more and 100 volume % or less), and is preferably 98 volume % or more, more preferably 99 volume % or more, and particularly preferably 99.5 volume % or more.
[0128] The inert atmosphere is substantially free of reducing gas. The content of reducing gas in the inert atmosphere may be 1% by volume or less, and preferably 0.5% by volume or less, and particularly preferably 0% by volume. The carbon support loaded with catalyst metal particles to be heated in the inert atmosphere in the second step preferably does not generate reducing gas by heating in the second step (e.g., by thermal decomposition).
[0129] Preferably, the inert atmosphere contains substantially no oxygen. That is, the oxygen content in the inert atmosphere may be, for example, 3 volume % or less, and preferably 1 volume % or less, particularly preferably 0 volume % or less.
[0130] The carbon support having the catalyst metal particles supported thereon to be heated in the inert atmosphere in the second step is preferably a dry solid. That is, for example, when the carbon support having the catalyst metal particles supported thereon is obtained in a solid form by the gas phase reduction treatment in the first step, in the second step, the carbon support having the catalyst metal particles supported thereon is heated in the inert atmosphere while remaining solid without being immersed in a liquid phase.
[0131] The temperature at which the carbon support on which the catalyst metal particles are supported is heated in the second step (hereinafter referred to as the "second heating temperature") may be, for example, 500°C or higher, and is preferably 600°C or higher, more preferably 700°C or higher, still more preferably 750°C or higher, and particularly preferably 800°C or higher. The upper limit value of the second heating temperature is not particularly limited, but the second heating temperature may be, for example, 1200°C or lower, and is preferably 1100°C or lower, and particularly preferably 1000°C or lower. The second heating temperature may be specified by arbitrarily combining any one of the above lower limits and any one of the above upper limits.
[0132] The time period for heating the carbon support on which the catalyst metal particles are loaded at the above-mentioned second heating temperature in the second step (hereinafter referred to as the "second heating time") is not particularly limited as long as the second heating time falls within the range of obtaining the effect of the present invention, but may be, for example, 1 minute or longer, and preferably 10 minutes or longer, particularly preferably 20 minutes or longer. The upper limit value of the second heating time is not particularly limited, but the second heating time may be, for example, 240 minutes or shorter, and preferably 120 minutes or shorter, particularly preferably 60 minutes or shorter. The second heating time may be specified by arbitrarily combining any one of the above-mentioned lower limit values and any one of the above-mentioned upper limit values.
[0133] It is preferable to adopt a relatively high temperature as each of the first heating temperature in the first step and the second heating temperature in the second step. That is, the first heating temperature and the second heating temperature are, for example, each preferably 500°C or higher (e.g., 500°C or higher and 1,200°C or lower), each more preferably 700°C or higher (e.g., 700°C or higher and 1,200°C or lower), each still more preferably 775°C or higher (e.g., 775°C or higher and 1,200°C or lower), each particularly preferably 800°C or higher (e.g., 800°C or higher and 1,200°C or lower).
[0134] When a relatively high temperature is adopted as each of the first heating temperature and the second heating temperature, it is possible to allow burying of the catalyst metal particles in the inner surface of the pores of the carbon carrier to be effectively performed while effectively preventing excessive aggregation of the catalyst metal particles.
[0135] It is preferred to adopt a temperature close to the first heating temperature in the first step as the second heating temperature in the second step. That is, the difference between the first heating temperature and the second heating temperature is, for example, preferably 300°C or less, more preferably 200°C or less, still more preferably 150°C or less, and particularly preferably 100°C or less.
[0136] It is preferred that the second step be performed without significantly lowering the temperature of the atmosphere after the gas phase reduction treatment in the first step. That is, between the end of heating at the first heating temperature in the first step and the start of heating at the second heating temperature in the second step, the temperature of the atmosphere in which the carbon support supporting the catalyst metal particles is maintained is preferably not lowered by 800° C. or more from the first heating temperature, more preferably not lowered by 500° C. or more, still more preferably not lowered by 200° C. or more, and particularly preferably not lowered by 100° C. or more.
[0137] In the method of the present invention, it is preferred that the first step is carried out in a predetermined container, and then, while the carbon support carrying the catalyst metal particles thereon is maintained in the container, the reducing atmosphere in the container is replaced with an inert atmosphere, and the second step is carried out in the container.
[0138] As described above, when the first step and the second step are continuously performed in the same container, the catalyst metal particles can be partially buried in the inner surface of the pores of the carbon support without oxidizing the surface of the catalyst metal particles. That is, while maintaining the durability of the catalyst metal particles, the catalyst metal particles can be partially buried in the inner surface of the pores of the carbon support.
[0139] In the method of the present invention, the carbon support on which the precursor compound is supported may not be subjected to liquid-phase reduction treatment before the first step and / or before the second step.
[0140] Here, "liquid phase reduction" is a method including reducing a precursor compound supported on a carbon support in a liquid phase to form catalyst metal particles supported on the carbon support. Specifically, in the liquid phase reduction treatment, for example, a reducing agent is added to a solution containing a carbon support supported with a precursor compound, and the mixture is maintained at a predetermined temperature for a predetermined period of time, thereby forming catalyst metal particles supported on the carbon support in the solution.
[0141] The battery electrode according to an embodiment of the present invention (hereinafter referred to as "the electrode of the present invention") includes the catalyst of the present invention. That is, the electrode of the present invention is, for example, a battery electrode including an electrode substrate and the catalyst of the present invention supported on the electrode substrate. The electrode of the present invention is, for example, an electrode for a fuel cell (e.g., a polymer electrolyte fuel cell), an air battery, a water electrolyzer (e.g., a polymer electrolyte water electrolyzer), a redox flow battery, or a halogen battery.
[0142] In addition, the electrode of the present invention is, for example, a cathode or an anode, preferably a cathode. That is, the electrode of the present invention is a cathode or an anode of a fuel cell, an air battery, a water electrolyzer, a redox flow battery, or a halogen battery, preferably a fuel cell cathode, an air battery cathode, a water electrolyzer cathode, a redox flow battery cathode, or a halogen battery cathode, more preferably a fuel cell cathode or an air battery cathode, and particularly preferably a fuel cell cathode.
[0143] A battery according to an embodiment of the present invention (hereinafter referred to as "battery of the present invention") includes an electrode of the present invention. That is, the battery of the present invention is, for example, a fuel cell (e.g., a polymer electrolyte fuel cell), an air battery, a redox flow battery, or a halogen battery including an electrode of the present invention. The battery of the present invention may include a membrane electrode assembly (MEA) including an electrode of the present invention.
[0144] The battery of the present invention is a battery comprising the electrode of the present invention as a cathode or anode, preferably a battery comprising the electrode of the present invention as a cathode. That is, the battery of the present invention is a fuel cell, an air battery, a redox flow battery or a halogen battery comprising the electrode of the present invention as a cathode or anode, preferably a fuel cell, an air battery, a redox flow battery or a halogen battery comprising the electrode of the present invention as a cathode, and more preferably a fuel cell comprising the electrode of the present invention as a cathode.
[0145] Next, specific examples according to the embodiments of the present invention will be described.
[0146] Example
[0147] [Carbon support A]
[0148] 1.0 g of polyacrylonitrile (PAN), 1.0 g of 2-methylimidazole, 6.0 g of zinc chloride (ZnCl2) and 30 g of dimethylformamide were mixed. The solvent was removed from the resulting mixture by drying. The dried mixture was heated in the atmosphere to undergo an infusibility treatment at 250°C.
[0149] Carbonization was performed by heating the infusible mixture at a gauge pressure of 0.90 MPa in a nitrogen atmosphere and maintaining it at 1500°C. Dilute hydrochloric acid was added to the carbonized material obtained by carbonization, and the mixture was stirred. Thereafter, the suspension containing the carbonized material was filtered using a filter membrane, and the carbonized material was washed with distilled water until the filtrate became neutral. In this way, metal removal treatment was performed by washing with acid.
[0150] The carbonized material after the metal removal treatment was pulverized with a fine pulverizer until its median particle size reached 0.4 μm or less. The pulverized carbonized material was vacuum dried to remove water. Thereafter, the carbonized material was subjected to a heat treatment at 300° C. in a nitrogen atmosphere. The carbonized material thus obtained was used as a carbon support A.
[0151] [Carbon support B]
[0152] 1.0 g of PAN, 1.0 g of 2-methylimidazole, 6.0 g of ZnCl2, 0.18 g of iron (III) chloride hexahydrate (FeCl3·6H2O) and 30 g of dimethylformamide were mixed. The solvent was removed from the resulting mixture by drying. The dried mixture was heated in the atmosphere to be subjected to an infusibility treatment at 250°C.
[0153] The infusible mixture was carbonized by heating the infusible mixture at a gauge pressure of 0.90 MPa in a nitrogen atmosphere and maintaining it at 1,300°C. Dilute hydrochloric acid was added to the carbonized material obtained by carbonization, and the mixture was stirred. Thereafter, the suspension containing the carbonized material was filtered using a filter membrane, and the carbonized material was washed with distilled water until the filtrate became neutral. In this way, metal removal treatment was performed by washing with an acid.
[0154] The carbonized material after the metal removal treatment was pulverized with a fine pulverizer until its median particle size reached 1 μm or less. The pulverized carbonized material was vacuum dried to remove water. Thereafter, the carbonized material was subjected to a heat treatment at 300° C. in a nitrogen atmosphere. In addition, the heat-treated carbonized material was heated and maintained at 900° C. under an ammonia stream, and thus the carbonized material was subjected to a nitrogen doping treatment and an activation treatment. The carbonized material thus obtained was used as a carbon support B.
[0155] [Carbon Support C]
[0156] As the carbon support C, commercially available Ketjen Black EC600JD (manufactured by Lion Specialty Chemicals Co., Ltd.) was used.
[0157] [Carbon Support D]
[0158] 1.0 g of PAN, 1.0 g of 2-methylimidazole, 6.0 g of ZnCl2 and 30 g of dimethylformamide were mixed. The solvent was removed from the resulting mixture by drying. The dried mixture was heated in the atmosphere to undergo an infusibility treatment at 250°C.
[0159] The infusible mixture was carbonized by heating the infusible mixture at normal pressure in a nitrogen atmosphere and maintaining it at 1,500°C. Dilute hydrochloric acid was added to the carbonized material obtained by carbonization, and the mixture was stirred. Thereafter, the suspension containing the carbonized material was filtered by using a filter membrane, and the carbonized material was washed with distilled water until the filtrate became neutral. In this way, metal removal treatment was performed by washing with an acid.
[0160] The carbonized material after the metal removal treatment was pulverized with a fine pulverizer until its median particle size reached 0.4 μm or less. The pulverized carbonized material was vacuum dried to remove water. Thereafter, the carbonized material was subjected to a heat treatment at 300° C. in a nitrogen atmosphere. The carbonized material thus obtained was used as a carbon support D.
[0161] [Example 1]
[0162] The metal-supported catalyst was prepared by applying method A of supporting catalyst metal particles on carbon support A. Specifically, carbon support A and an aqueous solution containing chloroplatinic acid (HPtCl) used as a platinum precursor and cobalt chloride (CoCl) used as an alloy component precursor were mixed for 18 hours. Thereafter, the resulting mixed liquid was dried in air at 100°C and further maintained in nitrogen at 150°C to volatilize the solvent component.
[0163] The obtained solid was subjected to heat treatment in a hydrogen atmosphere (hydrogen: 100% by volume) at 825° C. for 20 minutes (gas phase reduction treatment). Subsequently, while the temperature of the atmosphere was maintained in the range of 820° C. to 830° C., the hydrogen atmosphere was replaced with a nitrogen atmosphere (nitrogen: 100% by volume), and the solid was subjected to heat treatment in the nitrogen atmosphere at 825° C. for 40 minutes.
[0164] In order to remove unnecessary metals other than platinum alloy from the metal-supported catalyst thus obtained, the metal-supported catalyst and a 10% nitric acid solution were mixed for 2 hours. Thereafter, the metal-supported catalyst and the acid solution were separated by filtration, and further, the metal-supported catalyst was washed with distilled water until the filtrate became neutral. The washed metal-supported catalyst was dried in a vacuum at 60° C. to remove water.
[0165] After that, in order to remove nitric acid, the metal-supported catalyst was subjected to heat treatment in nitrogen at 300° C. In addition, in order to reduce and remove platinum oxide, the metal-supported catalyst was subjected to heat treatment in nitrogen at 700° C. Thus, a platinum alloy-supported catalyst formed of a carbon support A and platinum alloy particles supported on the carbon support A was obtained. The loading amount of platinum in the metal-supported catalyst finally obtained (the ratio of the weight of platinum contained in the metal-supported catalyst to the weight of the metal-supported catalyst) was 40% by weight. In addition, the noble metal / non-noble metal molar ratio (specifically, Pt / Co molar ratio) in the metal-supported catalyst was 7.0.
[0166] [Example 2]
[0167] The metal-supported catalyst was prepared by applying method B of supporting catalyst metal particles on carbon support A. Specifically, carbon support A and an aqueous solution containing H2PtCl6 were mixed for 18 hours. Thereafter, the resulting mixed liquid was dried in air at 100°C and further maintained in nitrogen at 150°C to volatilize the solvent component.
[0168] The obtained solid was subjected to heat treatment in a hydrogen atmosphere (hydrogen: 100% by volume) at 825° C. for 20 minutes. Subsequently, while the temperature of the atmosphere was maintained in the range of 820° C. to 830° C., the hydrogen atmosphere was replaced with a nitrogen atmosphere (nitrogen: 100% by volume), and the solid was subjected to heat treatment in a nitrogen atmosphere at 825° C. for 40 minutes. Thus, a platinum-supported catalyst formed of the carbon support A and pure platinum particles supported on the carbon support A was obtained. The loading amount of platinum in the metal-supported catalyst finally obtained was 40% by weight.
[0169] [Example 3]
[0170] The metal-supported catalyst was prepared by applying method C of supporting catalyst metal particles on carbon support A. Specifically, carbon support A and an aqueous solution containing H2PtCl6 were mixed for 18 hours. Thereafter, the resulting mixed liquid was dried in air at 100°C and further maintained in nitrogen at 150°C to volatilize the solvent component.
[0171] The obtained solid was subjected to heat treatment in a hydrogen atmosphere (hydrogen: 100% by volume) at 825° C. for 30 minutes. Subsequently, while the temperature of the atmosphere was maintained in the range of 820° C. to 830° C., the hydrogen atmosphere was replaced with a nitrogen atmosphere (nitrogen: 100% by volume), and the solid was subjected to heat treatment in a nitrogen atmosphere at 825° C. for 30 minutes. Thus, a platinum-supported catalyst formed of the carbon support A and pure platinum particles supported on the carbon support A was obtained. The loading amount of platinum in the metal-supported catalyst finally obtained was 40% by weight.
[0172] [Example 4]
[0173] The metal-supported catalyst was prepared by applying method E of supporting catalyst metal particles on carbon support A. Specifically, carbon support B and an aqueous solution containing H2PtCl6 and CoCl2 were mixed for 18 hours. Thereafter, the resulting mixed liquid was dried in air at 100°C and further maintained in nitrogen at 150°C to volatilize the solvent component.
[0174] The obtained solid was subjected to heat treatment in a hydrogen atmosphere (hydrogen: 100% by volume) at 825° C. for 60 minutes. In order to remove unnecessary metals other than the platinum alloy from the metal-supported catalyst thus obtained, the metal-supported catalyst and a 10% nitric acid solution were mixed for 2 hours. Thereafter, the metal-supported catalyst and the acid solution were separated by filtration, and further, the metal-supported catalyst was washed with distilled water until the filtrate became neutral. The washed metal-supported catalyst was dried in a vacuum at 60° C. to remove water.
[0175] After that, in order to remove nitric acid, the metal-supported catalyst was subjected to heat treatment in nitrogen at 300° C. In addition, in order to reduce and remove platinum oxide, the metal-supported catalyst was subjected to heat treatment in nitrogen at 700° C. Thus, a platinum alloy-supported catalyst formed of carbon support B and platinum alloy particles supported on carbon support B was obtained. The loading amount of platinum in the metal-supported catalyst finally obtained was 40% by weight. In addition, the noble metal / non-noble metal molar ratio (specifically, Pt / Co molar ratio) in the metal-supported catalyst was 7.0.
[0176] [Example C1]
[0177] A metal-supported catalyst is prepared by applying method D of supporting catalyst metal particles on carbon support B. Specifically, a platinum alloy-supported catalyst formed by carbon support B and platinum alloy particles supported on carbon support B is obtained in the same manner as in Example 4 above, except that carbon support B is used instead of carbon support A, and heat treatment is performed in a hydrogen atmosphere (hydrogen: 100 volume %) at 900°C for 60 minutes instead of in a hydrogen atmosphere at 825°C for 60 minutes. The loading amount of platinum in the metal-supported catalyst finally obtained is 30% by weight. In addition, the noble metal / non-noble metal molar ratio (specifically, Pt / Co molar ratio) in the metal-supported catalyst is 7.0.
[0178] [Example C2]
[0179] The metal-supported catalyst was prepared by applying the method B of supporting the catalyst metal particles on the carbon support C. Specifically, a platinum-supported catalyst formed of the carbon support C and pure platinum particles supported on the carbon support C was obtained in the same manner as in Example 2 above, except that the carbon support C was used instead of the carbon support A. The loading amount of platinum in the finally obtained metal-supported catalyst was 40% by weight.
[0180] [Example C3]
[0181] The high specific surface area (specific surface area: about 800m 2 / g to about 1,200m 2A commercially available platinum catalyst consisting of a carbon support of 1000 g / cm2 and pure platinum particles as catalyst metal particles supported on the carbon support was used as the metal-supported catalyst of Example C3. The loading amount of platinum in the metal-supported catalyst was 39 wt%.
[0182] [Example C4]
[0183] UNPC40-II (manufactured by Ishifuku Metal Industry Co., Ltd.), which is a commercially available platinum catalyst formed of a carbon support having a high specific surface area and pure platinum particles serving as catalyst metal particles supported on the carbon support, was used as the metal-supported catalyst of Example C4. The amount of platinum supported in the metal-supported catalyst was 34% by weight.
[0184] [Example C5]
[0185] A commercially available platinum catalyst formed of Vulcan XC72R (manufactured by Cabot Corporation) used as a carbon support and pure platinum particles used as catalyst metal particles supported on the carbon support was used as the metal-supported catalyst of Example C5. The loading amount of platinum in the metal-supported catalyst was 42% by weight.
[0186] [Example C6]
[0187] A metal-supported catalyst was prepared by applying method A of supporting catalyst metal particles on carbon support B. Specifically, a platinum alloy-supported catalyst formed of carbon support B and platinum alloy particles supported on carbon support B was obtained in the same manner as in Example 1 above, except that carbon support B was used instead of carbon support A. The loading amount of platinum in the metal-supported catalyst finally obtained was 30 wt %. In addition, the noble metal / non-noble metal molar ratio (specifically, Pt / Co molar ratio) in the metal-supported catalyst was 7.0.
[0188] [Example C7]
[0189] The metal-supported catalyst was prepared by applying method F of supporting catalyst metal particles on carbon support A. Specifically, carbon support A and an aqueous solution containing H2PtCl6 were mixed for 18 hours. Then, ethylene glycol was added as a reducing agent, and the resulting mixed solution was kept in air at 80°C for 4 hours, thereby performing a liquid phase reduction treatment.
[0190] Thereafter, the mixed liquid was dried in air at 100° C., and further maintained in nitrogen at 150° C. to volatilize the solvent component. Thus, a platinum-supported catalyst formed of the carbon support A and pure platinum particles supported on the carbon support A was obtained. The platinum loading in the finally obtained metal-supported catalyst was 40% by weight.
[0191] [Example C8]
[0192] A metal-supported catalyst is prepared by applying method G in which catalyst metal particles are supported on a carbon support A. Specifically, after the temperature is lowered to room temperature, a platinum-supported catalyst obtained by volatilizing the solvent component in the same manner as in Example C7 above is taken out into the atmosphere. Afterwards, the platinum-supported catalyst is subjected to a heat treatment at 900° C. for 60 minutes in a hydrogen atmosphere (hydrogen: 100% by volume). Thus, a platinum-supported catalyst formed of a carbon support A and pure platinum particles supported on the carbon support A is obtained. The loading amount of platinum in the metal-supported catalyst finally obtained is 40% by weight.
[0193] [Example C9]
[0194] A metal-supported catalyst was prepared by applying method A of supporting catalyst metal particles on carbon support D. Specifically, a platinum alloy-supported catalyst formed of carbon support D and platinum alloy particles supported on carbon support D was obtained in the same manner as in Example 1 above, except that carbon support D was used instead of carbon support A. The loading amount of platinum in the metal-supported catalyst finally obtained was 40 wt %. In addition, the noble metal / non-noble metal molar ratio (specifically, Pt / Co molar ratio) in the metal-supported catalyst was 7.0.
[0195] [Median diameter of carbon support]
[0196] The median diameter of the carbon carrier is measured. That is, for a carbon carrier that has not yet loaded with catalyst metal particles, by using a laser diffraction particle size distribution measuring device, particle size distribution data in which the horizontal axis represents the particle size (μm) and the vertical axis represents the cumulative relative particle amount (%) are obtained, and in the particle size distribution data, the particle size at which the cumulative relative particle amount reaches 50% is the median diameter (μm).
[0197] [Nitrogen content of carbon support and metal supported catalyst: elemental analysis (combustion method)]
[0198] Elemental analysis is performed by the combustion method of the carbon carrier and the metal-supported catalyst to measure each of the nitrogen content of the carbon carrier and the nitrogen content of the metal-supported catalyst. That is, by using an organic trace element analyzer (2400II, PerkinElmer Co., Ltd.), the nitrogen atom content of the carbon carrier that has not yet loaded the catalyst metal particles and the nitrogen atom content of the metal-supported catalyst are measured by the combustion method. Specifically, under the conditions of a combustion tube temperature of 980°C and a reduction tube temperature of 640°C, 2 mg of carbon carrier or 2 mg of metal-supported catalyst is analyzed by using helium as a carrier gas.
[0199] Then, the nitrogen atom content (weight %) of the carbon support is calculated by dividing the weight of the nitrogen atoms contained in the carbon support by the weight of the carbon support, and the obtained value is multiplied by 100. In addition, similarly, the weight of the nitrogen atoms contained in the metal-supported catalyst is divided by the weight of the metal-supported catalyst, and the obtained value is multiplied by 100 to calculate the nitrogen atom content (weight %) of the metal-supported catalyst.
[0200] [Metal content of metal-supported catalysts: Inductively coupled plasma mass spectrometry (ICP-MS)]
[0201] The noble metal content and non-noble metal content of the metal-supported catalyst are measured by ICP-MS. That is, first, 100 mg of the metal-supported catalyst is heated in an atmospheric atmosphere and kept at 800 ° C for 3 hours to remove the non-metallic components in the metal-supported catalyst. Then, the metal contained in the metal-supported catalyst is dissolved by immersing the metal-supported catalyst in 5 mL of aqua regia. Further, distilled water is added to dilute the resultant so that the total weight becomes 50 mL to obtain a metal solution. Afterwards, the noble metal concentration and non-noble metal concentration of the obtained metal solution are measured by using a sequential plasma emission spectrometer (ICPS-8100, manufactured by Shimadzu Corporation). Then, the noble metal concentration (mg / mL) and non-noble metal concentration (mg / mL) of the metal solution are multiplied by the volume (50 mL) of the metal solution to obtain the noble metal content (mg) and non-noble metal content (mg) of the metal-supported catalyst. Further, the noble metal content (mg) and the non-noble metal content (mg) of the metal-supported catalyst were divided by the weight of the metal-supported catalyst (i.e., 100 mg) and multiplied by 100 to calculate the noble metal content (wt %) and the non-noble metal content (wt %) obtained by ICP-MS.
[0202] The metal content (wt%) obtained by ICP-MS of a metal-supported catalyst is the content (wt%) of the metal of the catalyst metal particles contained in the metal-supported catalyst relative to the weight of the metal-supported catalyst. That is, when the catalyst metal particles contained in the metal-supported catalyst are formed only by precious metals, the content (wt%) of the precious metal in the metal-supported catalyst is the metal content (wt%) obtained by ICP-MS. In addition, when the catalyst metal particles contained in the metal-supported catalyst are formed by precious metals and non-precious metals, the sum of the content (wt%) of the precious metal in the metal-supported catalyst and the content (wt%) of the non-precious metal is the metal content (wt%) to be obtained by ICP-MS. Therefore, when the raw metal of the same kind as the metal used to form the catalyst metal particles is contained in the skeleton of the carbon carrier, the metal content (wt%) to be obtained by ICP-MS also includes the content (wt%) of the raw metal. At the same time, when the raw metal of the same kind as the metal used to form the catalyst metal particles is not contained in the skeleton of the carbon carrier, the metal content (wt%) to be obtained by ICP-MS does not include the content (wt%) of the raw metal.
[0203] [Specific surface area, average pore size, pore volume and hysteresis in adsorption isotherms of metal-supported catalysts: nitrogen adsorption method]
[0204] The specific surface area, average pore diameter, pore volume and hysteresis in an adsorption isotherm obtained by a nitrogen adsorption method of the metal-supported catalyst were measured by using a specific surface area / pore distribution measuring device (TriStar II 3020, manufactured by Shimadzu Corporation).
[0205] That is, first, 0.1 g of the metal-supported catalyst was heated at 100 °C and 6.7 × 10 -2 Pa for 3 hours to remove water adsorbed on the metal-supported catalyst. Then, a nitrogen adsorption isotherm at 77 K was obtained by the BET method. The nitrogen adsorption isotherm at 77 K was obtained by measuring the change in the amount of nitrogen adsorbed on the metal-supported catalyst associated with the change in nitrogen pressure at a temperature of 77 K.
[0206] exist Figure 2 In FIG. 1 , as an example of a nitrogen adsorption isotherm obtained at 77 K by the BET method, a nitrogen adsorption isotherm obtained for the metal-supported catalyst of Example 2 is shown. Figure 2 In the adsorption isotherm shown, the horizontal axis represents the relative pressure (P / P0), which is the ratio of the adsorption equilibrium pressure (P) to the saturated vapor pressure (P0) (for nitrogen at 77K, it is 1.01×10 5 Pa), and the vertical axis represents the nitrogen adsorption amount (cm 3 / g).
[0207] exist Figure 2 In the graph, the adsorption side isotherm (the adsorption isotherm measured when the relative pressure increases) and the desorption side isotherm (the adsorption isotherm measured when the relative pressure decreases) mostly overlap each other and there is hardly any hysteresis.
[0208] Here, in order to evaluate the magnitude of hysteresis in the nitrogen adsorption isotherm of the metal-supported catalyst, the N2 desorption / adsorption amount ratio was calculated for all measurement points where the relative pressure (P / P0) of the nitrogen adsorption isotherm was in the range of 0.4 or more and 0.6 or less.
[0209] In addition, the BET specific surface area (m2) of the metal-supported catalyst obtained by nitrogen adsorption method was obtained from the nitrogen adsorption isotherm at 77 K. 2 / g-metal-supported catalyst). The “ / g-metal-supported catalyst” in the numerical unit means that the value is per 1g of the metal-supported catalyst. Then, based on the specific surface area of the metal-supported catalyst and the above-mentioned metal content of the metal-supported catalyst obtained by ICP-MS, the specific surface area (m 2 / g-carbon support). That is, the specific surface area of the metal-supported catalyst (m 2 The specific surface area per 1 g of the carbon support (m / g-metal-supported catalyst) was divided by the weight ratio of the carbon support contained in the metal-supported catalyst calculated by the following equation: 2 / g-carbon support): weight ratio of the carbon support=1−(metal content (weight %) obtained by ICP-MS) / 100.
[0210] In addition, the volume of pores each having a pore diameter of 5 nm or more (5 nm or more pore volume) (cm 3 / g-metal-supported catalyst) and the volume of pores each having a pore diameter of less than 5 nm (pore volume less than 5 nm) (cm 3 / g-metal-supported catalyst). Then, in the same manner as the above-mentioned specific surface area, the pore volume (cm2) of 5 nm or more per 1 g of the carbon support contained in the metal-supported catalyst was calculated based on the metal content of the metal-supported catalyst obtained by ICP-MS. 3 / g-carbon support) and pore volume less than 5nm (cm 3 / g-carbon support).
[0211] In addition, the pore volume (cm 3 / g-carbon support) divided by the volume of pores 5 nm or larger (cm 3 / g carbon support), thereby calculating the volume ratio of pores smaller than 5 nm / pores 5 nm or larger.
[0212] In addition, the total pore volume (cm2) was obtained from the adsorption amount at the point where the relative pressure P / P0 of the nitrogen adsorption isotherm at 77 K was 0.98. 3 / g-metal-supported catalyst). In addition, in the same manner as the above-mentioned specific surface area, the total pore volume (cm2) per 1 g of the carbon support contained in the metal-supported catalyst was calculated based on the metal content of the metal-supported catalyst obtained by ICP-MS. 3 / g-carbon support). The average pore size (nm) of the metal-supported catalyst was then calculated by using analysis software (TriStar II 3020) included in a commercially available automatic specific surface area measuring device (TriStar II 3020, manufactured by Shimadzu Corporation): Average pore size (nm) = 4×total pore volume (cm 3 / g-metal-supported catalyst)×10 21}Specific surface area (m 2 / g-metal-supported catalyst)×10 18 .
[0213] [Specific surface area of metal-supported catalyst: water vapor adsorption method]
[0214] The BET specific surface area obtained by the water vapor adsorption method of the metal-supported catalyst was measured by using a specific surface area / pore distribution measuring device (BELSORP max, manufactured by MicrotracBEL Corp.). That is, the BET specific surface area (m2) obtained by the water vapor adsorption method was calculated by the same method as the above-mentioned nitrogen adsorption method. 2 / g-metal-supported catalyst), except that the adsorbed species was changed from nitrogen to water vapor, and the measurement temperature was changed to 298 K. Further, in the same manner as in the case of the specific surface area obtained by the above-mentioned nitrogen adsorption method, the BET specific surface area (m2) obtained by the water vapor adsorption method per 1 g of the carbon support contained in the metal-supported catalyst was calculated based on the metal content of the metal-supported catalyst obtained by ICP-MS. 2 / g-carbon support). Then, the BET specific surface area (m 2 / g-carbon support) divided by the BET specific surface area (m 2 / g-carbon support), thereby calculating the water vapor-BET / N2-BET specific area ratio of the metal-supported catalyst.
[0215] [Raman spectroscopy]
[0216] The metal-supported catalyst was analyzed by Raman spectroscopy. Raman spectra were measured using a HORIBA micro-laser Raman spectrometer (LabRAM, HORIBA Jobin Yvon). The laser used for measurement had an excitation wavelength of 532 nm and an output of 50 mW, and was measured under conditions of exposure 90 seconds × integration 2 times through a neutral density filter D3 to obtain a Raman spectrum.
[0217] The obtained Raman spectra were baseline corrected. That is, the Raman shift (cm -1 ) at 600cm -1 Scattering intensity and Raman shift near -1 ) at 2,000cm -1 A straight line of nearby scattering intensities was determined as a baseline, and the baseline was subtracted from each intensity of the scattering spectrum, thereby performing a baseline correction.
[0218] Next, we identified the -1 Then, from the Raman shift (cm) corresponding to the intensity Id of the D band, -1 )Ad (D band peak intensity) minus the Raman shift corresponding to half the intensity of the D band Id (cm -1 )Bd, and thus the half-width at half maximum of the D band (hereinafter referred to as “Raman D half-width at half maximum”) (cm -1 )
[0219] Now, in Figure 3 In FIG. 1 , the results obtained by analyzing the Raman spectrum obtained by Raman spectroscopy of the metal-supported catalyst of Example 2 are shown as an example of Raman spectrum. Figure 3 In the figure, the horizontal axis represents the Raman shift (cm -1 ), the vertical axis represents the scattering intensity, the dotted line represents the baseline, and Ad represents the Raman shift corresponding to the peak of the D band (cm -1 ), and Bd represents a Raman shift (cm) corresponding to a Raman spectrum exhibiting half the intensity of the intensity Id of the D band on the low wave number side of Ad -1 In addition, the Raman D half-peak half-width of the metal-supported catalyst was calculated by the following equation: Raman D half-peak half-width (cm -1 )=Ad(cm -1 )–Bd(cm -1 ).
[0220] [Number average particle size and volume average particle size of catalyst metal particles: X-ray diffraction method (XRD)]
[0221] The number average particle size (nm) and volume average particle size (nm) of the catalyst metal particles were measured by X-ray diffraction. That is, first, a sample of the powdered metal-supported catalyst was placed in a recess (2 cm × 2 cm × 0.5 mm (thickness)) of a glass sample plate and pressed with a slide glass. Thus, the sample was uniformly filled into the recess so that the sample surface and the reference surface matched each other. Then, the glass sample plate was fixed on a wide-angle X-ray diffraction sample stage so that the shape of the filled sample would not collapse.
[0222] Then, powder X-ray diffraction (XRD) measurement was performed by using an X-ray diffractometer (Rigaku RINT2100 / PC, Rigaku Corporation). The voltage and current applied to the X-ray tube were set to 50 kV and 300 mA, respectively. The sampling interval was set to 0.1 °, the scanning speed was set to 1 ° / min, and the measurement angle range (2θ) was set to 5 ° to 90 °. CuKα was used as the incident X-ray. The sample thickness was set to 0.5 mm, and the divergence slit width β was set to 2 / 3 °.
[0223] The obtained X-ray diffraction pattern was peak separated by using a Gaussian function, and the crystallite diameter corresponding to each separated peak was determined by using the Scherrer equation. 3 ”) as a weight, and the obtained crystallite diameters are weighted averaged to calculate the number average particle size of the catalyst metal particles. At the same time, the volume average particle size of the catalyst metal particles is calculated by weighting the obtained crystallite diameters using the volume, i.e., the “peak area ratio”, as a weight.
[0224] Now, the method of determining the number average particle size (nm) and the volume average particle size (nm) will be described in more detail. When the metal-supported catalyst contains platinum particles (pure platinum particles and / or platinum alloy particles), in a powder X-ray diffraction pattern obtained by powder X-ray diffraction using CuKα rays, a platinum (111) diffraction line appears at a position where the diffraction angle (2θ) is around 40° (e.g., in the range of 36° to 44°).
[0225] In this regard, in a metal-supported catalyst containing a carbon support and platinum particles supported on the carbon support, a diffraction line having a peak at a position where the diffraction angle (2θ) is around 40° appears in the X-ray diffraction pattern. In addition, the diffraction line includes a diffraction line derived from pure platinum and / or a platinum alloy and a diffraction line derived from the carbon structure of the carbon support.
[0226] The diffraction line derived from pure platinum is defined as a diffraction line having a peak at a position where the diffraction angle (2θ) is 39.6° or more and less than 39.8°. The diffraction line derived from a platinum alloy is defined as a diffraction line having a peak at a position where the diffraction angle (2θ) is 39.9° or more and less than 43.0°. The diffraction line derived from the carbon structure of the carbon support is defined as a diffraction line having a peak at a position where the diffraction angle (2θ) is 43.3° or more and less than 43.7°.
[0227] When the metal-loaded catalyst contains a plurality of platinum alloys with different compositions and / or crystal structures, a plurality of diffraction lines originating from the platinum alloys will appear. The diffraction angle at which the peak of the diffraction line originating from the platinum alloy is located is determined by its composition and crystal structure. For example, a diffraction line originating from a cobalt-platinum alloy represented by the composition of CoPt is defined as a diffraction line having a peak at a position where the diffraction angle is 41.1° or greater and less than 41.5°. In addition, a diffraction line originating from a cobalt-platinum alloy represented by the composition of CoPt3 is defined as a diffraction line having a peak at a position where the diffraction angle is 40.1° or greater and less than 40.5°. Further, a diffraction line originating from a cobalt-platinum alloy represented by the composition of CoPt7 is defined as a diffraction line having a peak at a position where the diffraction angle is 39.9° or greater and less than 40.1°.
[0228] In addition, when the metal-supported catalyst contains a plurality of platinum particles having the same composition and crystal structure and different crystallite diameters, a plurality of diffraction lines appear, each of which has a peak top located at the same diffraction angle position and has a different half-maximum full width.
[0229] In fact, in the XRD pattern obtained for the metal-supported catalyst, the platinum (111) diffraction line appears at a position where the diffraction angle (2θ) is around 40°. Therefore, baseline correction is first performed. That is, a straight line connecting the diffraction intensity at a diffraction angle (2θ) of around 35° to 37° and the diffraction intensity at a diffraction angle (2θ) of around 50° to 52° is determined as a baseline, and the baseline is subtracted from each intensity of the diffraction line, thereby performing baseline correction.
[0230] Next, the baseline-corrected diffraction line is separated into peaks originating from one or more pure Pt, peaks originating from one or more Pt alloys, and peaks originating from carbon. The diffraction line is separated by assuming that each of the multiple peaks obtained by separation is represented by a Gaussian function and optimizing the intensity, diffraction angle of the peak top, and half-maximum full width of each of the Gaussian functions of the multiple peaks, so that for all diffraction angles, the residual square sum obtained by adding the sum of the intensities of the diffraction line and the square of the difference (residual) of each intensity of the multiple peaks at each diffraction angle of the XRD pattern becomes the minimum.
[0231] exist Figure 4, the peak separation results obtained for the metal-loaded catalyst of Example 2 are shown as examples of the results obtained by peak separation of the (111) diffraction line of platinum having a peak top at a position in the diffraction angle (2θ) of around 40° (in the range of 36° to 44°) in the X-ray diffraction pattern.
[0232] In the XRD pattern of the metal-supported catalyst of Example 2 obtained by powder XRD measurement, as shown in FIG. Figure 4 As shown, after baseline correction, a diffraction line with a peak appears at a position where the diffraction angle (2θ) is 39.7°. The shape of the middle part of the diffraction line is significantly smaller than the shape of the lower part in terms of width, and the shape of the upper part is even smaller than the shape of the middle part in terms of width. Because of this, it is believed that when the diffraction angle (2θ) is near 40°, the diffraction line of the first platinum with a relatively large half-maximum full width, the diffraction line of the second platinum different from the first platinum in terms of crystallite diameter and having a smaller half-maximum full width, and the diffraction line of the third platinum different from the first and second platinum in terms of crystallite diameter and having an even smaller half-maximum full width overlapping each other. In addition, the metal-supported catalyst contains a carbon support, and therefore the diffraction line derived from carbon appears at a diffraction angle (2θ) near 43.5°.
[0233] In view of the above situation, if Figure 4 As shown, a diffraction line having a diffraction angle (2θ) near 40° is separated into four components consisting of a peak derived from the first platinum, a peak derived from the second platinum, a peak derived from the third platinum, and a peak derived from carbon by the above-mentioned peak separation method.
[0234] exist Figure 4 , the diffraction line “after baseline correction” represents the diffraction line obtained by performing baseline correction on the diffraction line obtained by XRD measurement, and the peak of “Pt1”, the peak of “Pt2”, the peak of “Pt3” and the peak of “carbon” respectively represent the peak originating from the first platinum, the peak originating from the second platinum, the peak originating from the third platinum and the peak originating from carbon obtained by peak separation of the diffraction line “after baseline correction”.
[0235] Then, the crystallite diameter of each of the first platinum particle, the second platinum particle, and the third platinum particle is calculated by the following Scherrer equation: Crystallite diameter = Kλ / βcosθ. Here, in the Scherrer equation, K represents the Scherrer constant (0.94), λ represents the wavelength of the CuKα ray (0.15418 nm), β represents the half-maximum full width (radian), and θ represents the diffraction angle (radian). That is, for example, by Figure 4The diffraction angle and the half-maximum full width of the isolated peak of "Pt1" in the XRD pattern shown were substituted into the above Scherrer equation to calculate the crystallite diameter of the first platinum particle. As a result, the crystallite diameter of the first platinum particle was calculated to be 2.91 nm, the crystallite diameter of the second platinum particle was calculated to be 6.32 nm, and the crystallite diameter of the third platinum particle was calculated to be 24.22 nm.
[0236] In addition, the peak area ratio (%) of each of the Pt separation peaks was calculated by dividing the corresponding areas of the three Pt separation peaks obtained by the above peak separation (i.e., the peak area of "Pt1", the peak area of "Pt2", and the peak area of "Pt3") by the sum of the areas of the three Pt separation peaks and multiplying by 100. As a result, the peak area ratio of the first platinum particle was calculated to be 87.0%, the peak area ratio of the second platinum particle was calculated to be 10.8%, and the peak area ratio of the third platinum particle was calculated to be 2.2%.
[0237] Then, using those peak area ratios as weights, the volume average particle size of the catalyst metal particles was calculated by weighted averaging. Specifically, the volume average particle size of the platinum particles supported on the metal-supported catalyst of Example 2 was calculated to be 3.75 nm by the following equation: Volume Average Particle Size (nm) = {(2.91×87.0)+(6.32×10.8)+(24.22×2.2)} / (87.0+10.8+2.2).
[0238] By using the peak area ratio / crystallite diameter 3 " is used as a weight to calculate the number average particle size of the catalyst metal particles. Specifically, the number average particle size of the platinum particles supported on the metal-supported catalyst of Example 2 is calculated to be 2.95 nm by the following equation: Number average particle size (nm) = {(2.91×87.0 / 2.91 3 )+(6.32×10.8 / 6.32 3 )+(24.22×2.2 / 24.2 3 )} / (87.0 / 2.91 3 +10.8 / 6.32 3 +2.2 / 24.2 3 ).
[0239] [Distribution of Catalyst Metal Particles in Metal-Supported Catalysts: Electron Beam Tomography]
[0240] The distribution of catalyst metal particles in the metal-supported catalyst is evaluated by electron beam tomography. That is, first, a scanning transmission electron microscope (STEM) (JEM-ARM200F, manufactured by JEOL Ltd.) is used to obtain a particle image of the metal-supported catalyst. The sample is dispersed in pure water, and then the dispersion is placed on a Cu net with a carbon support film, and the resultant is fixed to the sample stage. During observation, the sample stage is tilted from +78 ° to –78 ° (step angle: 2 °), so a metal-supported catalyst particle is observed from multiple angles to obtain multiple STEM particle images. Observation is performed under the condition of an observation magnification of 800,000 times to 1,000,000 times.
[0241] After that, multiple STEM particle images obtained by observation from multiple angles are reconstructed using 3D reconstruction software to obtain a three-dimensional reconstructed particle image of the metal-supported catalyst particles (hereinafter referred to as "3D particle image"). That is, by using 3D reconstruction software, multiple STEM particle images are aligned at the same site and the rotation axis is aligned, and Fourier transform is performed, and then multiple Fourier images are formed and inverse Fourier transform is performed to obtain a 3D particle image. Figure 5 , an example of a 3D particle image of the metal-supported catalyst of Example 3 obtained from the Z-axis direction is shown. Figure 5 In the figure, the numerical units shown on the X-axis and the Y-axis are nm.
[0242] In addition, by using 3D data analysis software, from the 3D particle image of the metal-loaded catalyst particles, the particularly bright part is determined as the catalyst metal particle, the bright part is determined as the carbon carrier, and the dark part is determined as the hole, so as to obtain a 3D reconstructed image showing only the catalyst metal particles, a 3D reconstructed image showing only the carbon carrier, and a 3D reconstructed image showing only the hole part of the carbon carrier. Then, by using 3D data analysis software, in the 3D reconstructed image of the metal-loaded catalyst particles, the X-axis and the Y-axis are fixed, and the position in the Z-axis direction is changed only with an increment of about 0.5nm to generate a cross-sectional particle image (catalyst metal particle image in a plane parallel to the XY plane) at each Z-axis position. About 200 to about 350 such cross-sectional particle images are generated for a metal-loaded catalyst particle.
[0243] Then, by using image analysis software, the 3D particle image of the catalyst particles of the metal load and the respective cross-sectional particle image are respectively subjected to image analysis to determine the position of the catalyst metal particles. Further, the depth position of the catalyst metal particles from the outer surface of the carbon carrier is determined. Then, the number of catalyst metal particles loaded on the outer surface of the carbon carrier and the number of catalyst metal particles loaded at a position with a predetermined depth from the outer surface (inside the carbon carrier) are counted respectively.
[0244] The catalyst metal particles loaded inside the carbon carrier are identified as particles that are not identified on the surface of the 3D reconstructed image obtained by superimposing the 3D reconstructed image of the carbon carrier and the 3D reconstructed image of the pore portion of the carbon carrier on the 3D reconstructed image of the catalyst metal particles. At the same time, the catalyst metal particles loaded on the outer surface of the carbon carrier are identified as particles other than the catalyst metal particles loaded inside the carbon carrier. For the distribution of catalyst metal particles in the metal-loaded catalyst, metal particles each having a particle size (e.g., a particle size of 1 nm or more) that can be identified by image analysis are used as analysis objects. The depth of the position where the catalyst metal particles are loaded inside the carbon carrier is defined as the shortest distance between the outer surface of the carbon carrier and the surface of the catalyst metal particles. Specifically, when the shortest distance between the surface of the catalyst metal particles and the outer surface of the carbon carrier is 20 nm or more, the catalyst metal particles are identified as loaded at a position having a depth of 20 nm or more from the surface of the carbon carrier.
[0245] The ratio of the number of catalyst metal particles loaded at a depth of 20 nm or more from the outer surface of the carbon support of the metal-loaded catalyst to the total number of catalyst metal particles loaded on the carbon support ("catalyst metal loading ratio at a depth of 20 nm or more") was calculated by the following equation: "catalyst metal loading ratio at a depth of 20 nm or more (%) = "number of catalyst metal particles loaded at a depth of 20 nm or more from the outer surface of the carbon support" ÷ "total number of catalyst metal particles loaded on the carbon support" × 100.
[0246] The ratio of the number of catalyst metal particles loaded on the outer surface of the carbon carrier of the metal-loaded catalyst to the total number of catalyst metal particles loaded on the carbon carrier (catalyst metal loading ratio at the outer surface) is calculated by the following equation: Catalyst metal loading ratio at the outer surface (%) = "the number of catalyst metal particles loaded on the outer surface of the carbon carrier" ÷ "the total number of catalyst metal particles loaded on the carbon carrier" × 100.
[0247] The ratio of the sum of the number of catalyst metal particles loaded on the outer surface of the carbon carrier of the metal-loaded catalyst and the number of catalyst metal particles loaded at a position having a depth of 5 nm or less from the outer surface to the total number of catalyst metal particles loaded on the carbon carrier ("catalyst metal loading ratio at a depth of +5 nm or less on the outer surface") is calculated by the following equation: "catalyst metal loading ratio at a depth of +5 nm or less on the outer surface (%) = "the number of catalyst metal particles loaded on the outer surface of the carbon carrier" + "the number of catalyst metal particles loaded at a position having a depth of 5 nm or less from the outer surface of the carbon carrier" ÷ "the total number of catalyst metal particles loaded on the carbon carrier" × 100.
[0248] [Tortuosity of Metal-Supported Catalysts: Electron Beam Tomography]
[0249] The tortuosity of the metal-supported catalyst was measured by electron beam tomography. That is, first, as described above, a 3D particle image of the metal-supported catalyst was obtained by electron beam tomography, and then a 3D reconstructed image showing only the carbon support portion was obtained from the 3D particle image by using 3D data analysis software. Fig. 6A , an example of a 3D reconstructed image of a carbon support portion obtained for the metal-supported catalyst of Example 3 is shown.
[0250] Then, a cube having a size of about 20 nm to about 40 nm on one side is cut out from the 3D reconstructed image of the carbon support portion as a 3D reconstructed image of a portion of the interior of the carbon support. Figure 6B In the figure, it is shown that Fig. 6A The 3D reconstructed image of a portion of the carbon carrier cut out from the 3D reconstructed image of the entire carbon carrier shown. That is, Figure 6B The cube shown in corresponds to Fig. 6A The small white cube part is brightly shown in FIG.
[0251] After that, the 3D reconstructed image of the cube is cut in each axis direction of the X-axis, Y-axis, and Z-axis of the three-dimensional orthogonal coordinates to obtain a cross-sectional image. Here, the cross-sectional image is binarized so that the skeleton of the carbon carrier is displayed in black and any other part, that is, the void part or the catalyst metal particle part is displayed in white. Figure 6C , an example of each of the X-axis cross-sectional image, the Y-axis cross-sectional image, and the Z-axis cross-sectional image is shown, each of which is obtained from Figure 6B The cube shown in FIG. 1 is cut out from the 3D reconstructed image and binarized.
[0252] Then, a line connecting the center points of the white parts in the cross-sectional image is determined as a gap path. Fig.6D In, will be Figure 6CMultiple void paths identified in one of the cross-sectional images shown are shown as white lines. Fig. 6E In FIG. 1 , an example of determining a gap path is schematically shown. Fig. 6E In the figure, the skeleton part of the carbon carrier is shown in black, the pore part is shown in white, and the void path is shown as a line connecting the center points of the pores. Then, the tortuosity of the metal-supported catalyst is calculated by the following equation: Tortuousness = f / s ("f" represents the length of the void path from one face of the cube to another face opposite to the above face, and "s" represents the length of the straight line connecting the point of the void path on one face and its point on the other face (the shortest straight line distance)). Fig. 6F , the length "f" of a void path (dashed line) in the 3D image of the cube and the shortest straight-line distance "s" of the void path are schematically shown. The tortuosity of each metal-supported catalyst is obtained as an arithmetic mean by: in a cube of a 3D reconstructed image of a carbon support obtained from a 3D particle image, a plurality of void paths are identified, each void path connecting a point on a face and a point on another face opposite thereto in each of the X-axis direction, the Y-axis direction, and the Z-axis direction; the tortuosity of each of the plurality of void paths is calculated; and the sum of the tortuosity of the void paths is divided by the number of void paths.
[0253] [Performance evaluation of batteries including electrodes containing metal-supported catalysts]
[0254] The performance of the fuel cell including the cathode containing the metal-loaded catalyst is evaluated. Specifically, first, a battery cathode with a catalyst layer is manufactured, and the catalyst layer contains a metal-loaded catalyst formed thereon. That is, an electrolyte (EW700) of such an amount of 0.9 with a weight ratio of the carbon support is added to 0.25g of the metal-loaded catalyst, and 2g of distilled water and 1-propanol are added to prepare an electrolyte solution. The electrolyte solution and 25g balls are loaded into a tank and mixed with a ball mill at 200rpm for 50 minutes to obtain a slurry composition for a catalyst layer containing a uniformly dispersed metal-loaded catalyst.
[0255] The obtained slurry composition for a catalyst layer was applied to a gas diffusion layer ("29BC", manufactured by SGL Carbon Japan Co., Ltd.) having an area of 5 cm 2 The area (2.3 cm × 2.3 cm) was such that the content of the catalyst metal particles supported on the metal-supported catalyst per unit area of the battery electrode became 0.2 mg / cm 2 , and dried to form a catalyst layer on the gas diffusion layer. Thus, a battery electrode having a catalyst layer containing a metal-supported catalyst formed thereon is obtained.
[0256] Next, a fuel cell including a cell electrode having a catalyst layer containing a metal-supported catalyst formed thereon is manufactured. That is, a cell electrode including the catalyst layer (positive electrode catalyst layer) manufactured as described above is used as a positive electrode.
[0257] Meanwhile, a negative electrode was manufactured as described below. 0.5 g of Pt / C (catalyst containing platinum particles supported on a carbon support: UNPC40-II, manufactured by Ishifuku Metal Industry Co., Ltd.), 10 g of 5% NAFION (trademark), 2 g of distilled water and 25 g of balls were charged into a jar and mixed with a ball mill at 200 rpm for 50 minutes to prepare a slurry Pt / C composition. A negative electrode including a catalyst layer (negative electrode catalyst layer) formed of a slurry Pt / C composition was manufactured in the same manner as the above-mentioned positive electrode, except that the Pt / C composition was applied to a gas diffusion layer (5 cm 2 ) so that the amount of Pt / C applied per unit area becomes 0.1 mg / cm 2 .
[0258] Then, a polymer electrolyte membrane ("NAFION (trademark) 211", manufactured by DuPont) was provided between the above-mentioned positive electrode catalyst layer and the above-mentioned negative electrode catalyst layer, and the resultant was subjected to pressure bonding at 150°C and 1MPa for 3 minutes, thereby manufacturing an MEA. A pair of gaskets were bonded to the MEA, and the resulting MEA was sandwiched between a pair of separators, thereby manufacturing a fuel cell unit cell. Afterwards, the unit cell manufactured as described above was installed in a fuel cell automatic evaluation system (manufactured by Toyo Corporation). A power generation test was first performed, and then a durability test was performed.
[0259] In the power generation test, saturated humidified air (oxygen) was supplied to the positive electrode side of the unit cell at 2.5 L / min (relative humidity: 100%) under a back pressure of 70 kPa, and saturated humidified hydrogen was supplied to the negative electrode side of the unit cell at 1.0 L / min, the cell temperature was set to 75°C (relative humidity: 100%), and the open circuit voltage was measured for 5 minutes. After that, the cell current density was increased from 4.0 A / cm 2 To 0A / cm 2 Each current density was maintained for 3 min and the cell voltage was measured.
[0260] Then, the output density obtained from the potential and current density was calculated for each potential, and the highest value was measured as the maximum output density (mW / cm 2 ). In addition, record the 1.0A / cm at the start of the durability test. 2Voltage (mV) and 3.0A / cm 2 The voltage (mV) under.
[0261] After that, the cell temperature was set to 75° C. Under a back pressure of 35 kPa, saturated humidified nitrogen was supplied to both sides of the unit cell at 0.5 L / min (relative humidity: 100%), and saturated humidified hydrogen was supplied to the anode side of the unit cell at 0.5 L / min (relative humidity: 100%). The durability test was performed by repeating a rectangular wave cycle in which the potential was maintained at 0.6 V for 30 seconds and at 1.0 V for 60 seconds.
[0262] After the above rectangular wave cycle was repeated 2,100 times, the power generation test was performed again. 1.0A / cm after the durability test was recorded 2 Voltage (mV) and 3.0A / cm 2 Then, the 1.0A / cm2 voltage measured as the initial performance in the power generation test before the durability test was 2 Subtract the voltage (mV) of 1.0A / cm2 measured in the power generation test after the durability test from the voltage (mV) of 2 The value obtained by the voltage (mV) at 2,100 cycles (the voltage (mV) after 2,100 cycles) was taken as the 1.0 A / cm 2 Similarly, the voltage drop (mV) at 3.0 A / cm2 measured as the initial performance in the power generation test before the durability test was calculated. 2 Subtract the 3.0A / cm2 measured in the power generation test after the durability test from the voltage (mV) at 2 The value obtained by the voltage (mV) at 2,100 cycles (the voltage (mV) after 2,100 cycles) was taken as the value of 3.0 A / cm after 2,100 cycles. 2 The voltage drop under the condition (mV).
[0263] [Evaluation of catalytic activity of carbon supports]
[0264] The catalytic activity of the carbon support was evaluated by using a rotating ring disk electrode apparatus (RRDE-3A rotating ring disk electrode apparatus version 1.2, manufactured by BAS Inc.) and a dual electrochemical analyzer (CHI700C, manufactured by ALS Co., Ltd.).
[0265] That is, first, a rotating ring disk electrode device of a three-electrode system is manufactured, which includes a working electrode containing a carbon support (a carbon support on which no catalyst metal particles are loaded). Specifically, 5 mg of the carbon support, 50 μL of 5% NAFION (trademark) (manufactured by Sigma-Aldrich, NAFION perfluoro ion exchange resin, 5% solution (Product No.: 510211)), 400 μL of water and 100 μL of isopropanol are mixed to prepare a slurry. Next, the slurry is subjected to ultrasonic treatment for 10 minutes and then to a homogenizer treatment for 2 minutes. Then, the resulting slurry is applied to a working electrode (a ring disk electrode for RRDE-3A, a platinum ring gold disk electrode, a disk diameter: 4 mm, manufactured by BAS Inc.) so that the carbon support content per unit area of the electrode becomes 0.1 mg / cm 2 , and dried to produce a working electrode carrying a carbon support.
[0266] In addition, a platinum electrode (23 cm platinum counter electrode, manufactured by BAS Inc.) was used as a counter electrode, and a reversible hydrogen electrode (RHE) (storage type reversible hydrogen electrode, manufactured by EC Frontier Co., Ltd.) was used as a reference electrode. Thus, a rotating ring disk electrode device including a working electrode containing a carbon support, a platinum electrode used as a counter electrode, and a reversible hydrogen electrode (RHE) used as a reference electrode was obtained. In addition, a 0.1 M perchloric acid aqueous solution was used as an electrolytic solution.
[0267] Then, the catalytic activity was measured using the above-mentioned rotating ring disk electrode apparatus. That is, a rotating ring disk electrode apparatus of a three-electrode system (including a working electrode containing a carbon support) was used to perform linear sweep voltammetry under a nitrogen atmosphere (N2-LSV) and linear sweep voltammetry under an oxygen atmosphere (O2-LSV).
[0268] In N2-LSV, nitrogen bubbling was first performed for 10 minutes to remove oxygen from the electrolytic solution. After that, the electrode was rotated at a rotation speed of 1,600 rpm, and the current density was recorded as a function of potential when a potential scan was performed at a scan rate of 20 mV / sec (N2-LSV).
[0269] In O2-LSV, further, oxygen bubbling was then performed for 10 minutes to fill the electrolytic solution with saturated oxygen. Thereafter, the electrode was rotated at a rotation speed of 1,600 rpm, and the current density when a potential scan was performed at a scan rate of 20 mV / sec was recorded as a function of potential (O2-LSV).
[0270] Then, N2-LSV was subtracted from O2-LSV to obtain an oxygen reduction voltammogram. In the obtained oxygen reduction voltammogram, the values were marked so that the reduction current took a negative value and the oxidation current took a positive value.
[0271] From the oxygen reduction voltammogram thus obtained, –10 μA / cm 2 The voltage at which the reduction current flows (oxygen reduction starting potential E O2 )(V, relative to NHE), and the current density I when a voltage of 0.7 V (relative to NHE) is applied 0.7 (mA / cm 2 ), as an indicator of the catalytic activity of the carbon support itself.
[0272] [result]
[0273] exist Figure 7 In the figures, for each of Examples 1 to 4 and Examples C1 to C9, there are shown a method for producing a metal-loaded catalyst, evaluation results of the characteristics of the metal-loaded catalyst, evaluation results of the performance of a battery including the metal-loaded catalyst, and evaluation results of the catalytic activity of the carbon support itself.
[0274] exist Figure 7 In the "Catalyst metal particles buried in the inner surface of the pores" row, the evaluation result of whether the metal-supported catalyst includes catalyst metal particles partially buried in the inner surface of the pores of the carbon support.
[0275] In this evaluation, when the metal-loaded catalyst satisfies all three conditions (i.e., the condition of having a catalyst metal particle size / pore size ratio of 0.70 or greater and 1.30 or less, the condition of having a maximum value of the N2 desorption / adsorption amount ratio of 1.05 or less, and the condition of having a catalyst metal loading ratio at the outer surface of 33% or less), the metal-loaded catalyst is judged to include catalyst metal particles partially buried in the inner surface of the pores of the carbon carrier, and is marked with the symbol "○" in the "Catalyst metal particles buried in the inner surface of the pores" row, and when the metal-loaded catalyst does not satisfy one or more of the three conditions, the metal-loaded catalyst is judged to not include catalyst metal particles partially buried in the inner surface of the pores of the carbon carrier, and is marked with the symbol "×" in this row.
[0276] like Figure 7 As shown, the performance of each of the cells including the metal-supported catalysts of Examples 1 to 4 was significantly better than that of each of Examples C1 to C9. That is, the cells including the metal-supported catalysts of Examples 1 to 4 each exhibited 1,255 mW / cm 2 or greater maximum output density, at 1.0A / cm in durability test 2The voltage drop was 31 mV or less at a current density of 3.0 A / cm 2 The voltage drop was 26 mV or less at a current density of 1.5 %.
[0277] In this regard, the metal-loaded catalysts of Examples 1 to 4 satisfy all of the conditions of having a catalyst metal particle size / pore size ratio of 0.70 or greater and 1.30 or less, the condition of having a maximum value of the N2 desorption / adsorption amount ratio of 1.05 or less, and the condition of having a catalyst metal loading ratio at the outer surface of 33% or less, while the metal-loaded catalysts of Examples C2 to C5 and C7 to C9 do not satisfy one or more of these three conditions.
[0278] That is, the metal-loaded catalysts of Examples C2 to C5 and C8 do not satisfy the above-mentioned conditions of the catalyst metal particle size / pore size ratio, the metal-loaded catalysts of Examples C2 to C4 and C9 do not satisfy the above-mentioned conditions of the N2 desorption / adsorption amount ratio, and the metal-loaded catalysts of Example C2, Example C3, and Example C7 to Example C9 do not satisfy the above-mentioned conditions of the catalyst metal loading ratio at the outer surface.
[0279] In addition, the metal-supported catalysts of Examples 1 to 4 further satisfy the requirement of having a catalyst content of 53.0 cm -1 The metal-supported catalysts of Examples C1 to C6 and C9 do not satisfy the condition of a Raman D half-peak half width of 0.04077 W or less.
[0280] That is, in Examples C1 and C6 respectively using carbon carrier B, Example C2 using carbon carrier C, Example C9 using carbon catalyst D, and Examples C3 to C5 using commercially available products, the Raman D half-peak half-width is greater than those of Examples 1 to 4, C7 and C8 respectively using carbon catalyst A.
[0281] In addition, the maximum values of the N2 desorption / adsorption amount ratios of the carbon carrier C used in Example C2 and the carbon carrier D used in Example C9 were 1.23 and 1.06, respectively. That is, the carbon carrier C and the carbon carrier D were inferior to the carbon carrier A and the carbon carrier B in terms of pore interconnectivity. The median diameter of the carbon carrier B used in Examples C1 and C6 was 0.58 μm, which was larger than the median diameter of the carbon carrier A.
[0282] In addition, although the metal-supported catalysts of Examples C7 and C8 included the carbon support A as in Examples 1 to 4, the performance of each of the cells including the metal-supported catalysts of Examples C7 and C8 was inferior to that of each of the cells including the metal-supported catalysts of Examples 1 to 4. One of the reasons for this is considered to be that in the production of the metal-supported catalysts of Examples C7 and C8, liquid phase reduction treatment was performed using Methods F and G for supporting catalyst metal particles.
[0283] The performance of each of the cells including the metal-supported catalysts of Examples 1, 2, and 3 was particularly excellent. That is, the performance of each of the cells including the metal-supported catalysts of Examples 1, 2, and 3 was better than that of Example 4. Specifically, the cells including the metal-supported catalysts of Examples 1, 2, and 3 each exhibited 1,315 mW / cm 2 or greater maximum output density, at 1.0A / cm in durability test 2 The voltage drop was 25 mV or less at a current density of 3.0 A / cm 2 The voltage drop was 19 mV or less at a current density of 1.5 %.
[0284] In this regard, the number average particle size of the catalyst metal particles supported on the metal-supported catalyst of Example 4 was 3.12 nm, while those of Examples 1, 2, and 3 were smaller. In addition, the volume average particle size of the catalyst metal particles supported on the metal-supported catalyst of Example 4 was 5.55 nm, while those of Examples 1, 2, and 3 were smaller. In addition, the metal-supported catalyst of Example 4 had a catalyst metal loading ratio at the outer surface of 32%, while those of Examples 1, 2, and 3 were smaller.
[0285] In the production of the metal-supported catalyst of Example 4, method E of supporting catalyst metal particles was used to perform gas phase reduction treatment for a longer period of time, and no heating treatment was performed in an inert atmosphere thereafter, so it is believed that aggregation of catalyst metal particles occurs during the gas phase reduction treatment.
[0286] In addition, the evaluation results of the catalytic activity exhibited by the carbon support alone without supporting the catalyst metal particles are as follows. Carbon support A exhibited an oxygen reduction onset potential E of 0.76 (V, vs. NHE) O2 and –0.1(mA / cm 2 ) current density I 0.7 , carbon support B exhibits an oxygen reduction onset potential E of 0.83 (V, relative to NHE) O2 and –1.8 (mA / cm 2 ) current concentration I 0.7 , and carbon support D exhibited an E of 0.75 (V, relative to NHE) O2 and –0.1(mA / cm 2 ) current density I 0.7 At the same time, carbon support C exhibits an oxygen reduction onset potential E of 0.26 (V, relative to NHE) O2 , but shows zero (mA / cm 2 ) current density I 0.7 .
[0287] That is, carbon support A, carbon support B, and carbon support D each exhibited significant oxygen reduction activity alone, while carbon support C did not exhibit oxygen reduction activity. In the above measurement method, a slight oxygen reduction reaction occurs even in the absence of a catalyst. Therefore, it can be concluded that in the above measurement method, the carbon support exhibits oxygen reduction activity only when an oxygen reduction onset potential EO2 of 0.35 (V, relative to NHE) or more is obtained.
Claims
1. A metal-supported catalyst comprising: a carbon support; and Catalyst metal particles supported on the carbon support, wherein the metal-supported catalyst comprises a carbon structure, the carbon structure exhibiting a Raman spectrum having a wavelength of 1,340 cm -1 The half-maximum width of the D band near the peak is 53.0 cm -1 Below, and wherein the metal-supported catalyst comprises the catalyst metal particles partially buried in the inner surface of the pores of the carbon carrier, wherein the ratio of the number average particle size of the catalyst metal particles to the average pore size of the metal-supported catalyst is 0.70 or more and 1.30 or less, wherein when the relative pressure of the nitrogen adsorption isotherm of the metal supported catalyst is within the range of 0.4 or more and 0.6 or less, the maximum value of the ratio of the nitrogen adsorption amount of the desorption side isotherm to the nitrogen adsorption amount of the adsorption side isotherm is 1.05 or less, and wherein a ratio of the number of the catalytic metal particles supported on the outer surface of the carbon support to the total number of the catalytic metal particles supported on the carbon support is 33% or less. 2 . The metal-supported catalyst according to claim 1 , wherein the number average particle diameter of the catalyst metal particles is 1.50 nm or more and 4.00 nm or less. 3 . The metal-supported catalyst according to claim 1 , wherein the volume average particle diameter of the catalyst metal particles is 2.00 nm or more and 6.50 nm or less.
4. The metal supported catalyst according to claim 1 or 2, wherein the metal supported catalyst is obtained by nitrogen adsorption method with a m 2 The BET specific surface area of the carbon support is 200 or more.
5. The metal supported catalyst according to claim 1 or 2, wherein the metal supported catalyst is obtained by water vapor adsorption method with a m 2 The BET specific surface area in m / g-carbon carrier is consistent with that obtained by nitrogen adsorption method. 2 The ratio of the BET specific surface area of 1.34 g / g-carbon support is 0.080 or less. 6 . The metal-supported catalyst according to claim 1 , wherein the median diameter of the carbon support is 1.00 μm or less.
7. The metal-supported catalyst according to claim 1 or 2, wherein the pore size of the metal-supported catalyst is less than 5 nm. 3 / g-the volume of the carbon support is 0.50 or more.
8. The metal-supported catalyst according to claim 1 or 2, wherein the ratio of the volume of pores of the metal-supported catalyst whose pore diameters are all less than 5 nm to the volume of pores whose pore diameters are all 5 nm or more is 1.80 or more.
9. The metal-supported catalyst according to claim 1 or 2, wherein the ratio of the number of the catalyst metal particles supported at a position having a depth of 20 nm or more from the outer surface of the carbon support to the total number of the catalyst metal particles supported on the carbon support is 11% or more.
10. The metal supported catalyst according to claim 1 or 2, wherein the catalyst metal particles are platinum particles.
11. A battery electrode comprising the metal-supported catalyst according to any one of claims 1 to 10.
12. A battery comprising the battery electrode according to claim 11.
Citation Information
Patent Citations
Catalyst for solid polymer fuel cells and method for producing same
WO2019065443A1
Negative electrode material for nonaqueous secondary battery
CN102203989A
Support for catalyst supporting, material with supported catalyst, electrode, and cell
CN102648050A